Accuracy of Cuff-Measured Blood Pressure: Systematic Reviews and Meta-Analyses - Picone, Dean S.; Schultz, Martin G.; Otahal, Petr; Aakhus, Svend; Al-Jumaily, Ahmed M.; Black, J. Andrew; Bos, Willem J.; Chambers, John B.; Chen, Chen-Huan; Cheng, Hao-Min; Cremer, Antoine; Davies, Justin E.; et al. (Journal of the American College of Cardiology, 2017)
Hypertension (HTN) is the single greatest cardiovascular risk factor worldwide. HTN management is usually guided by brachial cuff blood pressure (BP), but questions have been raised regarding accuracy.This comprehensive analysis determined the accuracy of cuff BP and the consequent effect on BP classification compared with intra-arterial BP reference standards.Three individual participant data meta-analyses were conducted among studies (from the 1950s to 2016) that measured intra-arterial aortic BP, intra-arterial brachial BP, and cuff BP.A total of 74 studies with 3,073 participants were included. Intra-arterial brachial systolic blood pressure (SBP) was higher than aortic values (8.0 mm Hg; 95% confidence interval [CI]: 5.9 to 10.1 mm Hg; p < 0.0001) and intra-arterial brachial diastolic BP was lower than aortic values (-1.0 mm Hg; 95% CI: -2.0 to -0.1 mm Hg; p = 0.038). Cuff BP underestimated intra-arterial brachial SBP (-5.7 mm Hg; 95% CI: -8.0 to -3.5 mm Hg; p < 0.0001) but overestimated intra-arterial diastolic BP (5.5 mm Hg; 95% CI: 3.5 to 7.5 mm Hg; p < 0.0001). Cuff and intra-arterial aortic SBP showed a small mean difference (0.3 mm Hg; 95% CI: -1.5 to 2.1 mm Hg; p = 0.77) but poor agreement (mean absolute difference 8.0 mm Hg; 95% CI: 7.1 to 8.9 mm Hg). Concordance between BP classification using the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure cuff BP (normal, pre-HTN, and HTN stages 1 and 2) compared with intra-arterial brachial BP was 60%, 50%, 53%, and 80%, and using intra-arterial aortic BP was 79%, 57%, 52%, and 76%, respectively. Using revised intra-arterial thresholds based on cuff BP percentile rank, concordance between BP classification using cuff BP compared with intra-arterial brachial BP was 71%, 66%, 52%, and 76%, and using intra-arterial aortic BP was 74%, 61%, 56%, and 65%, respectively.Cuff BP has variable accuracy for measuring either brachial or aortic intra-arterial BP, and this adversely influences correct BP classification. These findings indicate that stronger accuracy standards for BP devices may improve cardiovascular risk management.
EVALuna2:3961

Adherence to Antihypertensive Medication in Treatment-Resistant Hypertension Undergoing Renal Denervation - Schmieder, Roland; Ott, Christian; Schmid, Andrea; Friedrich, Stefanie; Kistner, Iris; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Toennes, Stefan W. (Journal of the American Heart Association, 2016)
Adherence to medication has been repeatedly proposed to represent a major cause of treatment-resistant hypertension (TRH); however, treatment decisions such as treating TRH with renal denervation depend on accurate judgment of adherence. We carefully analyzed adherence rates to medication before and after renal denervation and its effect on blood pressure (BP) control.Eighty patients with TRH were included in 2 prospective observational studies that assessed the difference of potential antihypertensive and nephroprotective effects of renal denervation. To compare prescribed with actual medication intake (representing a measure of adherence), we analyzed urine samples collected at baseline and at 6 months after renal denervation for antihypertensive compounds or metabolites (by liquid chromatography-mass spectrometry). In addition to office BP, 24-hour ambulatory BP and central hemodynamics (central systolic pressure, central pulse pressure) were assessed. Informed consent for analyses of urine metabolites was obtained from 79 of 80 patients. Actual intake of all antihypertensive drugs was detected at baseline and at 6 months after renal denervation in 44 (56%) and 52 (66%) patients, respectively; 1 drug was missing in 22 (28%) and 17 (22%) patients, respectively, and >=2 drugs were missing in 13 (16%) and 10 (13%) patients, respectively. At baseline, 24-hour ambulatory BP (P=0.049) and central systolic BP (P=0.012) were higher in nonadherent patients. Adherence did not significantly change overall (McNemar-Bowker test, P=0.362). An increase in adherence was observed in 21 patients, and a decrease was observed in 11 patients. The decrease in 24-hour ambulatory BP was not different in those with stable adherence 6 months after renal denervation (n=41, -7±13 mm Hg) compared with those with increased adherence (n=21, -10±13 mm Hg) and decreased adherence (n=11, -7±14 mm Hg) (P>0.20). Our study is limited by the relatively small sample size and potentially by the specific health environment of our university center (Northern Bavaria, Germany).Nonadherence to medication among patients with TRH was relatively low: ?1 of 6 patients with TRH did not take >=2 of the prescribed drugs. Adherence pattern did not change significantly after renal denervation and had no impact on the overall observed BP changes, supporting the concept that renal denervation is an effective treatment in patients with TRH.URL: https://www.clinicaltrials.gov. Unique identifiers: NCT00888433, NCT01442883 and NCT01687725.
EVALuna2:3842

Afferent neurons of the kidney with impaired firing pattern in inflammation – role of sodium currents? - Lale, Nena; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Pflügers Archiv: European Journal of Physiology, 2023)
Peripheral neurons with renal afferents exhibit a predominantly tonic firing pattern of higher frequency that is reduced to low frequencies (phasic firing pattern) in renal inflammation. We wanted to test the hypothesis that the reduction in firing activity during inflammation is due to high-activity tonic neurons switching from higher to low frequencies depending on altered sodium currents. We identified and cultivated afferent sensory neurons with renal projections from the dorsal root ganglia (Th11-L2). Cultivated neurons were incubated with the chemokine CXCL1 (1,5 nmol/ml) for 12 h. We characterized neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., < 5 APs upon stimulation in the current clamp. Their membrane currents were investigated in a voltage clamp. Data analyzed: renal vs. non-renal and tonic vs. phasic neurons. Renal afferent neurons exposed to CXCL1 showed a decrease in tonic firing pattern (CXCL1: 35,6% vs. control: 57%, P < 0.05). Na+ and K+ currents were not different between control renal and non-renal DRG neurons. Phasic neurons exhibited higher Na+ and K+ currents than tonic resulting in shorter APs (3.7 ± 0.3 vs. 6.1 ± 0.6 ms, P < 0.01). In neurons incubated with CXCL1, Na+ and K+ peak current density increased in phasic (Na+: − 969 ± 47 vs. − 758 ± 47 nA/pF, P < 0.01; K+: 707 ± 22 vs. 558 ± 31 nA/pF, P < 0.01), but were unchanged in tonic neurons. Phasic neurons exposed to CXCL1 showed a broader range of Na+ currents ([− 365– − 1429 nA] vs. [− 412– − 4273 nA]; P < 0.05) similar to tonic neurons. After CXCL1 exposure, significant changes in phasic neurons were observed in sodium activation/inactivation as well as a wider distribution of Na+ currents characteristic of tonic neurons. These findings indicate a subgroup of tonic neurons besides mere tonic or phasic neurons exists able to exhibit a phasic activity pattern under pathological conditions.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Chemokine; Firing pattern; Phasic; Renal afferent nerve; Sodium currents; Tonic; Voltage-gated sodium channels

Afferent renal innervation in anti-Thy1.1 nephritis in rats - Rodionova, Kristina; Veelken, Roland; Hilgers, Karl Friedrich; Paulus, Eva Maria; Linz, Peter; Fischer, Michael J.M.; Schenker, Martina; Reeh, Peter; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; et al. (American Journal of Physiology-Renal Physiology, 2020)
Afferent renal nerves exhibit a dual function controlling central sympathetic outflow via afferent electrical activity and influencing intrarenal immunological processes by releasing peptides such as calcitonin gene-related peptide (CGRP). We tested the hypothesis that increased afferent and efferent renal nerve activity occur with augmented release of CGRP in anti-Thy1.1 nephritis, in which enhanced CGRP release exacerbates inflammation. Nephritis was induced in Sprague-Dawley rats by intravenous injection of OX-7 antibody (1.75 mg/kg), and animals were investigated neurophysiologically, electrophysiologically, and pathomorphologically 6 days later. Nephritic rats exhibited proteinuria (169.3 ± 10.2 mg/24 h) with increased efferent renal nerve activity (14.7 ± 0.9 bursts/s vs. control 11.5 ± 0.9 bursts/s, n = 11, P < 0.05). However, afferent renal nerve activity (in spikes/s) decreased in nephritis (8.0 ± 1.8 Hz vs. control 27.4 ± 4.1 Hz, n = 11, P < 0.05). In patch-clamp recordings, neurons with renal afferents from nephritic rats showed a lower frequency of high activity following electrical stimulation (43.4% vs. 66.4% in controls, P < 0.05). In vitro assays showed that renal tissue from nephritic rats exhibited increased CGRP release via spontaneous (14 ± 3 pg/mL vs. 6.8 ± 2.8 pg/ml in controls, n = 7, P < 0.05) and stimulated mechanisms. In nephritic animals, marked infiltration of macrophages in the interstitium (26 ± 4 cells/mm2) and glomeruli (3.7 ± 0.6 cells/glomerular cross-section) occurred. Pretreatment with the CGRP receptor antagonist CGRP8-37 reduced proteinuria, infiltration, and proliferation. In nephritic rats, it can be speculated that afferent renal nerves lose their ability to properly control efferent sympathetic nerve activity while influencing renal inflammation through increased CGRP release.
CRIS-Team Scopus Importer:2020-11-13
Keywords: afferent renal neerves; calcitonin gene-related peptide; renal inflammation; renal innervation; sympathetic innervation

Aktueller Standard der Blutdruckmessung – Stellungnahme der Deutschen Hochdruckliga e. V. DHL® – Deutsche Gesellschaft für Hypertonie und Prävention - Eckert, Siegfried; Ott, Christian; Büchner, Nikolaus; Dechend, Ralf; Lüders, Stephan; Mengden, Thomas; Sanner, Bernd (Deutsche Medizinische Wochenschrift, 2019)
Arterial hypertension is one of the most prevalent chronic diseases, and a major risk factor for cardiovascular diseases. It is essential to perform the blood pressure measurement under standardized conditions in the office/clinical setting, otherwise inaccuracy of blood pressure values may lead to poor blood pressure control or misdiagnosis. Compliance with these standards by a trained observer is of crucial importance for a reliable and accurate blood pressure measurement in clinical practice. Regardless of the standardized assessment, it has to be kept in mind that available devices on the market may not measure blood pressure accurate enough. Therefore, a validated (e.âŠg. German Hypertension League Quality Seal) blood pressure monitor should be used. Out-of-office (home and ambulatory) blood pressure measurements provide important information beyond determining resting office/clinical BP.
CRIS-Team Scopus Importer:2019-11-05
Keywords: blood pressure measurement; standard/standardized measurement; validation/validated devices

Angiotensin pathways under therapy with empagliflozin in patients with chronic heart failure - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Rauh, Manfred; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2023)
Aims: Large outcome studies demonstrated a reduction of heart failure hospitalization or cardiovascular death in patients with chronic heart failure (CHF). The renin–angiotensin system (RAS) is a key player in fluid and sodium regulation. The classic angiotensin-converting enzyme–angiotensin II–angiotensin-1 receptor axis (Ang I–ACE–Ang II receptor axis) is predominantly angiotensin II (Ang-II) induced and promotes vasoconstriction. In contrast, the angiotensin-converting-enzyme-2–angiotensin-(1-7)–Mas axis (Mas-axis) is mediated by the metabolites angiotensin-1-7 (Ang-(1-7)) and angtiotensin-1-5 (Ang-(1-5)) and exerts cardioprotective effects. Methods: We previously investigated the effect of empagliflozin on the systemic haemodynamic in patients with stable CHF (NYHA II–III) in a randomized placebo-controlled clinical trial ‘Analysing the Effect of Empagliflozin on Reduction of Tissue Sodium Content in Patients With Chronic Heart Failure (ELSI)’. In a post hoc analysis, we now analysed whether empagliflozin has an effect on the RAS by measuring detailed RAS profiles (LC-MS/MS-based approach) in 72 patients from ELSI. We compared RAS parameters after 1-month and 3-months treatment with empagliflozin or placebo to baseline. The secondary goal was to analyse whether the effect of empagliflozin on RAS parameters was dependent on angiotensin-receptor-blocking (ARB) or angiotensin-converting-enzyme-inhibitor (ACEI) co-medication. Results: Empagliflozin medication induced a significant rise in Ang-II [68.5 pmol/L (21.3–324.2) vs. 131.5 pmol/L (34.9–564.0), P = 0.001], angiotensin-I (Ang-I) [78.7 pmol/L (21.5–236.6) vs. 125.9 pmol/L (52.6–512.9), P < 0.001], Ang-(1-7) [3.0 pmol/L (3.0–15.0) vs. 10.1 pmol/L (3.0–31.3), P = 0.006], and Ang-(1-5) [5.4 pmol/L (2.0–22.9) vs. 9.9 pmol/L (2.8–36.4), P = 0.004], which was not observed in the placebo group (baseline to 3-months treatment). A significant rise in Ang-II (206.4 pmol/L (64.2–750.6) vs. 568.2 pmol/L (164.7–1616.4), P = 0.001), Ang-(1-7) (3.0 pmol/L (3.0–14.1) vs. 15.0 pmol/L (3.0–31.3), P = 0.017), and Ang-(1-5) [12.2 pmol/L (3.8–46.6) vs. 36.4 pmol/L (11.1–90.7), P = 0.001] under empagliflozin treatment was only seen in the subgroup of patients with ARB co-medication, whereas no change of Ang-II (16.7 pmol/L (2.0–60.8) vs. 26.4 pmol/L (10.7–63.4), P = 0.469), Ang-(1-7) (6.6 pmol/L (3.0–20.7) vs. 10.5 pmol/L (3.0–50.5), P = 0.221), and Ang-(1-5) (2.7 pmol/L (2.0–8.4) vs. 2.8 pmol/L (2.0–6.9), P = 0.851) was observed in patients with empagliflozin that were on ACEI co-medication (baseline to 3-months treatment). Conclusions: Our data indicate that empagliflozin might lead to an activation of both the Ang I–ACE–Ang II receptor axis and the Mas-axis pathway. Activation of the Ang I–ACE–Ang II receptor axis and the protective Mas-axis pathway after initiating treatment with empagliflozin was only seen in patients with ARB co-medication, in contrast to co-medication with ACEI.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Angiotensin profiles; Cardioprotective effects; Chronic heart failure; Empagliflozin; Renin–angiotensin system

ANGIOTENSIN PROFILES IN PATIENTS WITH HYPERTENSION AND TYPE 2 DIABETES WITH COMBINATION THERAPY OF EMPAGLIFLOZIN AND LINAGLIPTIN VERSUS METFORMIN AND INSULIN GLARGINE - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Ott, Christian; Pietschner, Robert; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2022-07-29

ANGIOTENSIN PROFILES IN PATIENTS WITH HYPERTENSION AND TYPE 2 DIABETES WITH COMBINATION THERAPY OF EMPAGLIFLOZIN AND LINAGLIPTIN VERSUS METFORMIN AND INSULIN GLARGINE - Bosch, Agnes; Poglitsch, Marko; Kannenkeril, Dennis; Ott, Christian; Pietschner, Robert; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: The renin-angiotensin system (RAS) plays a key role in the physiological regulation of blood pressure. Patients with type-2-diabetes-mellitus (T2DM) and hypertension are known to have increased RAS activity. However, the precise role of RAS activation after SGLT2-inhibitor therapy is unknown. The classic RAS comprises the ACE-AngII-AT1R-axis (classic-axis) that promotes vasoconstriction. The Angiotensin-converting-enzyme-2-angiotensin-(1-7)-Mas axis (Mas-axis) with its components Angiotensin-(1-7) (Ang-1-7) and Angiotensin-(1-5) (Ang-1-5) is an endogenous negative regulatory pathway of the classic-axis, which can reduce its harmful effects. DESIGN AND METHOD: Angiotensin profiles were determined in 55 patients with hypertension and T2DM from our double blind, randomized, placebo controlled clinical trial "Effects of Empagliflozin+Linagliptin (E+L) vs Metformin+Insulin Glargine (M+I) on Renal and Vascular Changes in Type 2 Diabetes'' (ELMI) at baseline and three months after application of either E+L or M+I. An LC-MS/MS based approach was used to simultaneously quantify individual angiotensin metabolites (Attoquant Diagnostics, Vienna, Austria). RESULTS: In the E+L group medication induced a rise in Ang-I, Ang-(1-7) and a trend to a rise in Ang-II between baseline and treatment, which was not present in the M+I group (table).Comparison between the E+L and M+I group revealed that change between baseline and treatment was significantly different for Ang I (p = 0.002) and Ang-(1-7) (p = 0.002) between the groups. No difference in change between baseline and treatment was found for Ang II (p = 0.182) and Ang-(1-5) (p = 0.224) between the E+L and M+I group. CONCLUSIONS: In patients with hypertension and T2DM three months of therapy with E+L led to a rise of classic and protective components of the RAS, which was not present in the M+I group. The biological consequence of this complex RAS activation remains to be elucidated.
CRIS-Team Scopus Importer:2022-09-09

Angiotensin profiles in patients with type 2 diabetes and combination therapy of empagliflozin and linagliptin versus metformin and insulin glargine - Bosch, Agnes; Poglitsch, M.; Kannenkeril, Dennis; Ott, Christian; Striepe, Kristina; Schmieder, Roland (DIABETOLOGIA, 2021)
CRIS-Team WoS Importer:2021-10-01

ANNOYANCE DUE TO NOISE TRIGGERS VASCULAR CHANGES IN THE RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Harazny, Joanna M.; Striepe, Kristina; Karg, Marina V.; Jung, Susanne; Kolwelter, Julie; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

APPLICATION OF A CENTRAL ILIAC ARTERIOVENOUS COUPLER DEVICE IN SEVERE TREATMENT-RESISTANT ARTERIAL HYPERTENSION: A FOUR-YEAR FOLLOW-UP - Jung, Susan; Ott, Christian; Karg, M.; Bosch, A.; Schmid, M.; Schlundt, Christian; Achenbach, Stephan; Schmieder, Roland (2018)
EVALuna2:35985

Application of a central iliac arteriovenous coupler device in severe treatment-resistant hypertension: a 3.5-year follow-up - Jung, Susanne; Ott, Christian; Karg, Marina V.; Bosch, Agnes; Schmid, Michael; Schlundt, Christian; Achenbach, Stephan; Schmieder, Roland (Journal of Hypertension, 2018)
OBJECTIVE: In patients with resistant hypertension, percutaneous placement of an iliac arteriovenous coupler device leads to a reduction of blood pressure (BP) via decreased total vascular resistance and improved arterial compliance. However, long-term efficacy and safety need to be further explored. We report on the first case of 3.5-year follow-up in a patient who underwent implantation of an iliac arteriovenous coupler device. RESULTS: A patient with resistant hypertension was admitted to hospital. Despite treatment with six anti-hypertensive drugs, his BP was poorly controlled. Previously, he had undergone renal denervation, which did not cause a significant BP decrease. Therefore, an arteriovenous coupler device was implanted, leading to an immediate and significant BP decrease. The patient was discharged with an office BP of 122/71 mmHg. After 3 months, there was a sustained BP decrease (-14/9 mmHg), whereas later, it was fluctuant (office BP: 147-173/85-95 mmHg, ABPM: 153-166/81-94 mmHg) probably due to medication non-adherence confirmed by a urinary toxicological screening test. Follow-up right heart catheterization showed changes in hemodynamic parameters related to volume congestion, which were accompanied by progressive dyspnea and weight gain. This was controlled by an optimized diuretic therapy. Additionally, an invasive closure maneuver was performed, leading to an immediate BP increase after closure and a similar decrease after re-opening of the anastomosis, verifying its proper long-term function. CONCLUSION: The implantation of an iliac arteriovenous coupler device appears to be a promising and effective method to decrease BP and therefore reduce cardiovascular risk in patients with severe, treatment-resistant hypertension.
EVALuna2:34505

A randomised study of the impact of the SGLT2 inhibitor dapagliflozin on microvascular and macrovascular circulation - Ott, Christian; Jumar, Agnes; Striepe, Kristina; Friedrich, Stefanie; Karg, Margarete; Bramlage, Peter; Schmieder, Roland (Cardiovascular Diabetology, 2017)
The sodium-glucose cotransporter 2 inhibitor, dapagliflozin, has been shown to improve diabetic control and reduce blood pressure in patients with type 2 diabetes mellitus. Its effects on micro- and macrovascular structure and function have not yet been reported.This was a prospective, single-centre, placebo-controlled, double-blind, randomised crossover phase IIIb study conducted between March 2014 and February 2015. After a 4-week run-in/washout phase, patients (N = 59) received 6 weeks of either dapagliflozin 10 mg or placebo once daily. They then underwent a 1-week washout before crossing over to the other treatment. Changes in retinal capillary flow (RCF) and arteriole remodelling were evaluated using scanning laser Doppler flowmetry, while micro- and macrovascular parameters in the systemic circulation were assessed using pulse wave analysis.Six weeks of dapagliflozin treatment resulted in improvements in diabetes control, including blood glucose and insulin resistance, and reduced office and 24-h ambulatory blood pressure values. RCF decreased from 324 AU at baseline to 308 AU after treatment with dapagliflozin (p = 0.028), while there was little difference after the placebo (318 AU; p = 0.334). Furthermore, the arteriole remodelling that was seen after the placebo phase was not evident after the dapagliflozin phase. Central systolic and diastolic blood pressure values were significantly lower after 6 weeks of dapagliflozin, by 3.0 and 2.2 mmHg, respectively (p = 0.035 and 0.020, respectively vs. baseline).Six weeks of dapagliflozin treatment resulted in numerous beneficial effects. In addition to achieving superior diabetes control and blood pressure, parameters associated with the early stages of vascular remodelling were also improved. Trial registration http://www.clinicaltrials.gov (NCT02383238).
EVALuna2:3943

Association of Noise Annoyance with Measured Renal Hemodynamic Changes - Kannenkeril, Dennis; Jung, Susanne; Ott, Christian; Striepe, Kristina; Kolwelter, Julie; Schmieder, Roland; Bosch, Agnes (Kidney & Blood Pressure Research, 2021)
Background: Chronic mental stress is recognized as a modifiable risk factor for cardiovascular disease. The aim of this study was to demonstrate that noise annoyance-induced stress is associated with changes in renal hemodynamics. Methods: Renal hemodynamic parameters were measured using steady-state input clearance with infusion of para-aminohippuric acid and inulin in individuals with normal, high normal, and elevated blood pressure. All individuals ranked subjective annoyance due to noise in everyday life on a 7-grade Likert scale. The median of all rankings was used as a cutoff point to divide the group into noise-annoyed and non-noise-annoyed individuals. Different renal hemodynamic parameters were calculated based on the Gomez equation. Results: Noise-annoyed individuals (n = 58) showed lower renal plasma flow (599 +/- 106 vs. 663 +/- 124 mL/min, p = 0.009), lower renal blood flow (1,068 +/- 203 vs. 1,172 +/- 225 mL/min, p = 0.047), higher filtration fraction (22.7 +/- 3.3 vs. 21.3 +/- 3.0, p = 0.012), higher renal vascular resistance (88.9 +/- 25.6 vs. 75.8 +/- 22.9 mm Hg/[mL/min], p = 0.002), and higher resistance of afferent arteriole (2,439.5 +/- 1,253.4 vs. 1,849.9 +/- 1,242.0 dyn s(-1) cm(-5), p = 0.001) compared to non-noise-annoyed individuals (n = 55). There was no difference in measured glomerular filtration rate (133 +/- 11.8 vs. 138 +/- 15 mL/min, p = 0.181), resistance of efferent arteriole (2,419.4 +/- 472.2 vs. 2,245.8 +/- 370.3 dyn s(-1) cm(-5), p = 0.060), and intraglomerular pressure (64.0 +/- 3.1 vs. 64.6 +/- 3.5 mm Hg, p = 0.298) between the groups. After adjusting for age, renal plasma flow, renal blood flow, and renal vascular resistance remained significantly different between the groups, with a trend in increased afferent arteriolar resistance and filtration fraction. Conclusion: In this study, noise annoyance was associated with reduced renal perfusion attributed to increased renal vascular resistance predominantly at the afferent site. Long-term consequences of this renal hemodynamic pattern due to noise annoyance need to be investigated.
CRIS-Team WoS Importer:2021-05-14

AT II Receptor Blockade and Renal Denervation: Different Interventions with Comparable Renal Effects? - Rodionova, Kristina; Hindermann, Martin; Hilgers, Karl Friedrich; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Kidney & Blood Pressure Research, 2021)
Background: Angiotensin II (Ang II) and the renal sympathetic nervous system exert a strong influence on renal sodium and water excretion. We tested the hypothesis that already low doses of an Ang II inhibitor (candesartan) will result in similar effects on tubular sodium and water reabsorption in congestive heart failure (CHF) as seen after renal denervation (DNX). Methods: Measurement of arterial blood pressure, heart rate (HR), renal sympathetic nerve activity (RSNA), glomerular filtration rate (GFR), renal plasma flow (RPF), urine volume, and urinary sodium. To assess neural control of volume homeostasis, 21 days after the induction of CHF via myocardial infarction rats underwent volume expansion (0.9% NaCL; 10% body weight) to decrease RSNA. CHF rat and controls with or without DNX or pretreated with the Ang II type-1 receptor antagonist candesartan (0.5 ug i.v.) were studied. Results: CHF rats excreted only 68 + 10.2% of the volume load (10% body weight) in 90 min. CHF rats pretreated with candesartan or after DNX excreted from 92 to 103% like controls. Decreases of RSNA induced by volume expansion were impaired in CHF rats but unaffected by candesartan pointing to an intrarenal drug effect. GFR and RPF were not significantly different in controls or CHF. Conclusion: The prominent function of increased RSNA - retaining salt and water - could no longer be observed after renal Ang II receptor blockade in CHF rats.
CRIS-Team WoS Importer:2021-06-11
Keywords: Renal sympathetic innervation; Angiotensin II; Congestive heart failure; Renal nerve ablation; Renal function

Basal nitric oxide activity is an independent determinant of arteriolar structure in the human retinal circulation - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Schneider, Markus; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2011)
Experimental data indicate that nitric oxide might play a role in structure and remodeling of peripheral small arteries and arterioles. We hypothesized that retinal arteriolar structure is modulated by basal nitric oxide activity.The study cohort comprised 97 male untreated patients with normal and elevated blood pressure but without clinical evidence for cardiovascular disease. The changes of retinal capillary blood flow (RCF) to nitric oxide synthase inhibitor N-monomethyl-L-arginine (L-NMMA), that reflects basal nitric oxide activity of retinal vasculature, and to flicker light, that in part nitric oxide dependently provokes retinal vasodilatation, and parameters of retinal arteriolar structure, for example wall-to-lumen ratio (WLR), were assessed noninvasively and in vivo by scanning laser Doppler flowmetry.Participants were stratified according to the median WLR of retinal arterioles into two groups. In the group with WLR above the median RCF in response to infusion of L-NMMA decreased to a smaller extent (-3.82 ± 26 vs. -26.0 ± 45 arbitrary units and -0.83 ± 8.4 vs. -5.88 ± 11%, P = 0.004 and P = 0.015; respectively), whereas RCF in response to flicker light did not differ significantly compared to the counter group (22.2 ± 56 vs. 39.8 ± 51 arbitrary units and 7.42 ± 15 vs. 11.9 ± 14%, P = 0.112 and P = 0.149). In the whole study cohort WLR of retinal arterioles was related with the decrease of RCF to L-NMMA infusion [when expressed in absolute terms (r = 0.252, P = 0.013) and in percentage change (r = 0.213, P = 0.036)] and inversely related with the change of RCF to flicker light [when expressed in absolute terms (r = -0.203, P = 0.048) but not clearly when expressed in percentage change (r = -0.161, P = 0.120)]. Adjustment for major cardiovascular risk factors and changes of systemic hemodynamics in response to L-NMMA infusion revealed an independent relationship between WLR of retinal arterioles and percentage change of RCF to L-NMMA infusion (ß = 0.300, P = 0.007).Basal nitric oxide activity emerged as an independent determinant of arteriolar remodeling in the human retinal circulation in vivo.
EVALuna2:3475

Blood pressure reduction after renal denervation in patients with or without chronic kidney disease - Günes-Altan, Merve; Schmid, Axel; Ott, Christian; Bosch, Agnes; Pietschner, Robert; Schiffer, Mario; Uder, Michael; Schmieder, Roland; Kannenkeril, Dennis (Clinical Kidney Journal, 2024)
Background. Renal denervation (RDN) has emerged as an adjacent option for the treatment of hypertension. This analysis of the Erlanger registry aimed to compare the blood pressure (BP)-lowering effects and safety of RDN in patients with and without chronic kidney disease (CKD). Methods. In this single-center retrospective analysis, 47 patients with and 127 without CKD underwent radiofrequency-, ultrasound- or alcohol-infusion-based RDN. Office and 24-h ambulatory BP and estimated glomerular filtration rate (eGFR) were measured at baseline, and after 6 and 12 months. Results. A total of 174 patients with a mean age of 59.0 ± 10 years were followed up for 12 months. At baseline, mean eGFR was 55.8 ± 21 mL/min/1.73 m2 in patients with CKD and 87.3 ± 13 mL/min/1.73 m2 in patients without CKD. There was no significant eGFR decline in either of the groups during 12 months of follow-up. In patients without CKD, office systolic and diastolic BP were reduced by –15.3 ± 17.5/–7.9 ± 10.8 mmHg 6 months after RDN and by –16.1 ± 18.2/–7.7 ± 9.6 mmHg 12 months after RDN. In patients with CKD, office systolic and diastolic BP were reduced by –10.7 ± 24.0/–5.8 ± 13.2 mmHg 6 months after RDN and by –15.1 ± 24.9/–5.9 ± 12.9 mmHg 12 months after RDN. Accordingly, in patients without CKD, 24-h ambulatory systolic and diastolic BP were reduced by –7.2 ± 15.8/–4.9 ± 8.8 mmHg 6 months after RDN and by –9.0 ± 17.0/–6.2 ± 9.8 mmHg 12 months after RDN. In patients with CKD, 24-h systolic and diastolic BP were reduced by –7.4 ± 12.9/–4.2 ± 9.9 mmHg 6 months after RDN and by –8.0 ± 14.0/–3.6 ± 9.6 mmHg 12 months after RDN. There was no difference in the reduction of office and 24-h ambulatory BP between the two groups at any time point (all P > .2). Similar results have been found for the 6 months data. With exception of rare local adverse events, we did not observe any safety signals. Conclusion. According to our single-center experience, we observed a similar reduction in 24-h, day and night-time ambulatory BP as well as in-office BP in patients with and without CKD at any time point up to 12 months. We conclude that RDN is an effective and safe treatment option for patients with hypertension and CKD.
CRIS-Team Scopus Importer:2024-01-26
Keywords: blood pressure; chronic kidney disease; hypertension; post-hoc analysis; renal denervation

BLOOD PRESSURE REDUCTION AFTER RENAL DENERVATION IN PATIENTS WITH OR WITHOUT CHRONIC KIDNEY DISEASE: THE ERLANGER EXPERIENCE - Schmid, Axel; Ott, Christian; Bosch, Agnes; Schiffer, Mario; Uder, Michael; Schmieder, Roland; Kannenkeril, Dennis (JOURNAL OF HYPERTENSION, 2023)
CRIS-Team WoS Importer:2023-03-17

CAN WE IDENTIFY GLOMERULAR HYPERFILTRATION IN PATIENTS WITH TYPE 2 DIABETES BY CLINICAL PARAMETERS? - Kolwelter, Julie; Striepe, Kristina; Kannenkeril, Dennis; Jung, Susanne; Bosch, Agnes; Ott, Christian; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Cardiovascular and health cost impacts of cuff blood pressure underestimation and overestimation of invasive aortic systolic blood pressure - Fonseca, Ricardo; Palmer, Andrew J.; Picone, Dean S.; Cox, Ingrid A.; Schultz, Martin G.; Black, J. Andrew; Bos, Willem J.W.; Cheng, Hao Min; Chen, Chen Huan; Cremer, Antoine; Dwyer, Nathan; Hughes, Alun D.; et al. (Journal of Hypertension, 2023)
OBJECTIVE: Hypertension management is directed by cuff blood pressure (BP), but this may be inaccurate, potentially influencing cardiovascular disease (CVD) events and health costs. This study aimed to determine the impact on CVD events and related costs of the differences between cuff and invasive SBP. METHODS: Microsimulations based on Markov modelling over one year were used to determine the differences in the number of CVD events (myocardial infarction or coronary death, stroke, atrial fibrillation or heart failure) predicted by Framingham risk and total CVD health costs based on cuff SBP compared with invasive (aortic) SBP. Modelling was based on international consortium data from 1678 participants undergoing cardiac catheterization and 30 separate studies. Cuff underestimation and overestimation were defined as cuff SBP less than invasive SBP and cuff SBP greater than invasive SBP, respectively. RESULTS: The proportion of people with cuff SBP underestimation versus overestimation progressively increased as SBP increased. This reached a maximum ratio of 16 : 1 in people with hypertension grades II and III. Both the number of CVD events missed (predominantly stroke, coronary death and myocardial infarction) and associated health costs increased stepwise across levels of SBP control, as cuff SBP underestimation increased. The maximum number of CVD events potentially missed (11.8/1000 patients) and highest costs (241 300 USD/1000 patients) were seen in people with hypertension grades II and III and with at least 15 mmHg of cuff SBP underestimation. CONCLUSION: Cuff SBP underestimation can result in potentially preventable CVD events being missed and major increases in health costs. These issues could be remedied with improved cuff SBP accuracy.
CRIS-Team Scopus Importer:2023-09-08

Central arteriovenous anastomosis for the treatment of patients with uncontrolled hypertension (the ROX CONTROL HTN study): a randomised controlled trial - Lobo, Melvin D.; Sobotka, Paul A.; Stanton, Alice; Cockcroft, John R.; Sulke, Neil; Dolan, Eamon; Van Der Giet, Markus; Hoyer, Joachim; Furniss, Stephen S.; Foran, John P.; Witkowski, Adam; Januszewicz, Andrzej; et al. (Lancet, 2015)
Hypertension contributes to cardiovascular morbidity and mortality. We assessed the safety and efficacy of a central iliac arteriovenous anastomosis to alter the mechanical arterial properties and reduce blood pressure in patients with uncontrolled hypertension.We enrolled patients in this open-label, multicentre, prospective, randomised, controlled trial between October, 2012, and April, 2014. Eligible patients had baseline office systolic blood pressure of 140 mm Hg or higher and average daytime ambulatory blood pressure of 135 mm Hg or higher systolic and 85 mm Hg or higher diastolic despite antihypertensive treatment. Patients were randomly allocated in a 1:1 ratio to undergo implantation of an arteriovenous coupler device plus current pharmaceutical treatment or to maintain current treatment alone (control). The primary endpoint was mean change from baseline in office and 24 h ambulatory systolic blood pressure at 6 months. Analysis was by modified intention to treat (all patients remaining in follow-up at 6 months). This trial is registered with ClinicalTrials.gov, number NCT01642498.83 (43%) of 195 patients screened were assigned arteriovenous coupler therapy (n=44) or normal care (n=39). Mean office systolic blood pressure reduced by 26·9 (SD 23·9) mm Hg in the arteriovenous coupler group (p<0·0001) and by 3·7 (21·2) mm Hg in the control group (p=0·31). Mean systolic 24 h ambulatory blood pressure reduced by 13·5 (18·8) mm Hg (p<0·0001) in arteriovenous coupler recipients and by 0·5 (15·8) mm Hg (p=0·86) in controls. Implantation of the arteriovenous coupler was associated with late ipsilateral venous stenosis in 12 (29%) of 42 patients and was treatable with venoplasty or stenting.Arteriovenous anastomosis was associated with significantly reduced blood pressure and hypertensive complications. This approach might be a useful adjunctive therapy for patients with uncontrolled hypertension.ROX Medical.
EVALuna2:3769

Central Iliac Arteriovenous Anastomosis for Uncontrolled Hypertension: One-Year Results From the ROX CONTROL HTN Trial - Lobo, Melvin D.; Ott, Christian; Sobotka, Paul A.; Saxena, Manish; Stanton, Alice; Cockcroft, John R.; Sulke, Neil; Dolan, Eamon; Van Der Giet, Markus; Hoyer, Joachim; Furniss, Stephen S.; Foran, John P.; et al. (Hypertension, 2017)
Creation of a central iliac arteriovenous anastomosis using a novel nitinol coupler device results in an immediate, significant reduction of blood pressure (BP). We present efficacy and safety findings at 12 months post-coupler insertion. This open-label, multicenter, prospective, randomized trial enrolled patients with a baseline office systolic BP >=140 mm Hg and average daytime ambulatory BP >=135/85 mm Hg. Subjects were randomly allocated to coupler implantation and continuing previous pharmacotherapy or to maintain previous treatment alone. At 12 months, 39 patients who had coupler therapy were included in the intention-to-treat analysis. Office-based systolic BP reduced by 25.1±23.3 mm Hg (baseline, 174±18 mm Hg; P<0.0001) post-coupler placement, and office diastolic BP reduced by 20.8±13.3 mm Hg (baseline, 100±13 mm Hg; P<0.0001). Mean 24-hour ambulatory BP reduced by 12.6±17.4/15.3±9.7 mm Hg (P<0.0001 for both). In a prespecified subset of patients who failed to respond adequately to prior renal denervation, coupler therapy led to highly significant reduction in office systolic/diastolic BP (30.7/24.1 mm Hg) and significant reduction in 24-hour ambulatory systolic/diastolic BP (12.4/14.4 mm Hg) at 12 months (n=9). After coupler therapy, 14 patients (33%) developed ipsilateral venous stenosis; all were treated successfully with venous stenting. These findings confirm the importance of arterial mechanics in the pathophysiology of hypertension and support the clinical use of a central iliac arteriovenous anastomosis.URL: http://www.clinicaltrials.gov. Unique identifier: NCT01642498.
EVALuna2:4029

Central pulse pressure is an independent determinant of vascular remodeling in the retinal circulation - Ott, Christian; Raff, Ulrike; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Hypertension, 2013)
Pulse pressure has been recognized as a risk factor for stroke. Moreover, it was shown that central pulse pressure relates more strongly to vascular disease and outcome than (peripheral) brachial pulse pressure. Because vascular remodeling in the retinal circulation mirrors the 1 in the cerebral circulation and represents an easy, noninvasive possibility to assess microvascular changes in humans, we analyzed the impact of central pulse pressure on retinal vascular structure in humans. The study cohort comprised 135 nondiabetic patients across a wide range of blood pressure values. Parameter of retinal arteriolar remodeling (wall-to-lumen ratio) was assessed noninvasively and in vivo by scanning laser Doppler flowmetry. Central pulse pressure and augmentation index normalized to a heart rate of 75 beats per minute were assessed by pulse wave analysis. Central pulse pressure correlated with wall-to-lumen ratio (r=0.302; P<0.001), central augmentation index normalized to a heart rate of 75 beats per minute correlated with wall-to-lumen ratio (r=0.190; P=0.028), and in accordance pulse pressure amplification (peripheral pulse pressure/central pulse pressure) was negatively correlated with wall-to-lumen ratio (r=-0.223; P=0.009). In contrast, central mean arterial pressure was not correlated with wall-to-lumen ratio (r=0.110; P=0.203). Multiple regression analysis revealed an independent relationship between wall-to-lumen ratio and central pulse pressure (?=0.277; P=0.009), but not with other classical cardiovascular risk factors. Thus, central pulse pressure, indicative of changes in large conduit arteries is an independent determinant of vascular remodeling in small retinal arterioles. Such a relationship indicates a coupling and crosstalk between the microvascular and macrovascular changes attributable to hypertension.
EVALuna2:3610

Central pulse pressure predicts BP reduction after renal denervation in patients with treatment-resistant hypertension - Ott, Christian; Schmid, Axel; Toennes, Stefan W.; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (EuroIntervention, 2015)
Enhanced vascular ageing is associated with elevated central pulse pressure (cPP), an independent predictor of cardiovascular (CV) events. Although antihypertensive treatment strategies are effective, high residual CV risk remains indicative of advanced and largely irreversible vascular damage. Renal denervation (RDN) has been shown to reduce blood pressure (BP) to various extents in patients with treatment-resistant hypertension (TRH). We hypothesised that cPP predicts BP reduction after RDN.Sixty-three patients with true TRH underwent catheter-based RDN using the Symplicity Flex(TM) catheter and were followed for six months. At baseline, cPP was assessed by pulse wave analysis (SphygmoCor(TM)). Patients were stratified according to their median cPP (55 mmHg), and called "low cPP" (below the median) or "high cPP" (above the median). Office BP reduction six months after RDN was greater (-22±19/-13±11 vs. -12±20/-5±13 mmHg, p=0.038/0.014) and 24-hr ambulatory blood pressure (ABP) reduction tended to be greater (-11±13/-8±10 vs. -3±18/-4±10 mmHg, p=0.070/0.112) in patients with low cPP compared to those with high cPP. Only cPP (?=0.687, p=0.001) and baseline systolic BP (?=-0.564, p<0.001) were independent determinants of office systolic BP reduction after RDN.Our data suggest that cPP, indicative of the degree of large arterial stiffening, may be helpful to identify responders to RDN.
EVALuna2:3764

Change of renal function after short-term use of cardioprotective agents in patients with type 2 diabetes is not accurately assessed by the change of estimated glomerular filtration rate: an observational study - Kolwelter, Julie; Striepe, Kristina; Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Schiffer, Mario; Schmieder, Roland (Diabetology & Metabolic Syndrome, 2022)
Background After initiating cardioprotective agents, a fall of estimated glomerular filtration rate (eGFR) has been reported in several studies. Our goal was to evaluate the accuracy of change of Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) eGFR in patients with type 2 diabetes (T2D) after short-term pharmacological intervention with angiotensin-converting enzyme inhibitor, angiotensin-receptor blocker, gliptin or sodium-glucose cotransporter-2 inhibitor. Methods We analyzed 190 patients with T2D in the early stage of the disease, having no overt renal impairment by CKD-EPI equation. In each patient, we measured GFR (mGFR) by applying the constant infusion input clearance technique with sinistrin (Inutest; Fresenius, Linz, Austria) at baseline and after short-term (4-12 weeks) pharmacological intervention with cardioprotective agents (ramipril, telmisartan, linagliptin, metformin, empagliflozin) that potentially lead to an alteration of renal function. Simultaneously, a standardized analysis of serum creatinine was performed and eGFR was estimated by the CKD-EPI equation. Results Average mGFR was 111 +/- 20 ml/min/1.73m(2), whereas eGFR was lower with 93 +/- 13 ml/min/1.73m(2). The ratio eGFR/mGFR in relation to mGFR was almost curvilinear, showing an underestimation of renal function by eGFR in the upper normal range. At baseline only 80 patients (42%) lay within +/- 10% of mGFR and the concordance correlation coefficient (CCC) was extremely low (- 0.07). After short-term pharmacological intervention changes in eGFR and mGFR correlated with each other (r = 0.286, p < 0.001). For example, for a given mGFR of 111 ml/min/1.73m(2), a change of mGFR by +/- 10% corresponded to +/- 11 ml/min/1.73m(2), but the confidence interval of eGFR was 25 ml/min/1.73m(2). The CCC was low (0.22). Conclusion The agreement between eGFR by CKD-EPI and mGFR is modest and the change of renal function after short-term pharmacological intervention is not accurately and precisely reflected by the change of eGFR in patients with T2D in the early stage of their disease.
CRIS-Team WoS Importer:2022-08-05

Circadian rhythm and day to day variability of serum potassium concentration: a pilot study - Schmidt, Stefan; Ditting, T.; Deutsch, Birgit; Schutte, R.; Friedrich, S.; Kistner, I.; Ott, Christian; Raff, U.; Veelken, Roland; Schmieder, Roland (Journal of Nephrology, 2015)
Hyperkalemia is a common and life-threatening complication frequently seen in patients with acute kidney injury, end-stage renal disease and chronic heart failure. Cardiac arrest and ventricular fibrillation are possible consequences. Biosensors are currently being developed to measure serum potassium under ambulatory conditions and trigger an alarm if the potassium concentration exceeds normal limits. Only few studies exist on the circadian rhythm of potassium; and its dependence on age and kidney function is less clear.Our observational monocentric exploratory study included 30 subjects of which 15 had impaired renal function (RF) (GFR <60 ml/min/1.73 m(2)). Subjects were further categorized into three age groups: 18-39 years (N normal RF = 5, N impaired RF = 4), 40-59 years (N normal RF = 5, N impaired RF = 6), 60-80 years (N normal RF = 5, N impaired RF = 5). Serum potassium levels were measured every 2 h during a 24 h period and repeated once after 2, 4, or 6 days.In the 15 subjects with normal RF, the lowest mean potassium level (3.96 ± 0.14 mmol/l) was observed at 9 p.m. and the greatest (4.23 ± 0.23 mmol/l) at 1 p.m. In patients with impaired RF the lowest mean potassium level (4.20 ± 0.32 mmol/l) was observed at 9 p.m. and the highest (4.57 ± 0.46 mmol/l) at 3 p.m. The range between the mean of minimum and maximum was greater in patients with impaired RF (0.71 ± 0.45 mmol/l) than in subjects with normal RF (0.53 ± 0.14 mmol/l) [p < 0.001]. No difference in the circadian rhythm was found between the first and second examination.Our results indicate that patients with normal and impaired RF have comparable circadian patterns of serum potassium concentrations, but higher fluctuations in patients with impaired RF. These results have clinical relevance for developing an automatic biosensor to measure the potassium concentration in blood under ambulatory conditions in patients at high risk for potassium fluctuations.
EVALuna2:3700

Combination of empagliflozin and linagliptin improves blood pressure and vascular function in type 2 diabetes - Jung, Susanne; Bosch, Agnes; Kannenkeril, Dennis; Karg, Marina V.; Striepe, Kristina; Bramlage, Peter; Ott, Christian; Schmieder, Roland; Jung, Susanne (European Heart Journal - Cardiovascular Pharmacotherapy, 2020)
AIMS: Preserved vascular function represents a key prognostic factor in type 2 diabetes mellitus (T2DM), but data on vascular parameters in this patient cohort are scarce. Patients with T2DM often need more than one drug to achieve optimal glucose control. The aim of this study was to analyse the efficacy of two combination therapies on vascular function in subjects with T2DM. METHODS AND RESULTS: This prospective, randomized study included 97 subjects with T2DM. Subjects were randomized to either the combination therapy empagliflozin (E) 10 mg with linagliptin (L) 5 mg once daily or metformin (M) 850 or 1000 mg twice daily with insulin glargine (I) once daily. At baseline and after 12 weeks, subjects had peripheral office and 24-h ambulatory blood pressure (BP) measurement and underwent vascular assessment by pulse wave analysis under office and ambulatory conditions. Office, 24-h ambulatory and central BP as well as pulse pressure (PP) decreased after 12 weeks of treatment with E + L, whereas no change was observed in M + I. There were greater decreases in 24-h ambulatory peripheral systolic (between-group difference: -5.2 ± 1.5 mmHg, P = 0.004), diastolic BP (-1.9 ± 1.0 mmHg, P = 0.036), and PP (-3.3 ± 1.0 mmHg, P = 0.007) in E + L than M + I. Central office systolic BP (-5.56 ± 1.9 mmHg, P = 0.009), forward pressure height of the pulse wave (-2.0 ± 0.9 mmHg, P = 0.028), 24-h ambulatory central systolic (-3.6 ± 1.4 mmHg, P = 0.045), diastolic BP (-1.95 ± 1.1 mmHg, P = 0.041), and 24-h pulse wave velocity (-0.14 ± 0.05m/s, P = 0.043) were reduced to a greater extent with E + L. CONCLUSION: Beyond the effects on glycaemic control, the combination therapy of E + L significantly improved central BP and vascular function compared with the classic combination of M + I. CLINICALTRIALS.GOV: NCT02752113.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Blood pressure; Central haemodynamics; Empagliflozin; Linagliptin; T2DM; Vascular function

Combined therapy of empagliflozin and linagliptin is superior to metformin and insulin glargine in improving blood pressure and vascular function in type 2 diabetes - Jung, Susanne; Bosch, Agnes; Kannenkeril, Dennis; Karg, M.; Striepe, Kristina; Bramlage, P.; Ott, Christian; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Complex reinnervation pattern after unilateral renal denervation in rats - Rodionova, Kristina; Fiedler, Christian; Günther, Franziska; Grouzmann, Eric; Neuhuber, Winfried; Fischer, Michael; Ott, Christian; Linz, Peter; Freisinger, Wolfgang; Heinlein, Sonja; Schmidt, Stefan; Schmieder, Roland; et al. (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2016)
Renal denervation (DNX) is a treatment for resistant arterial hypertension. Efferent sympathetic nerves regrow, but reinnervation by renal afferent nerves has only recently been shown in the renal pelvis of rats after unilateral DNX. We examined intrarenal perivascular afferent and sympathetic efferent nerves after unilateral surgical DNX. Tyrosine hydroxylase (TH), CGRP, and smooth muscle actin were identified in kidney sections from 12 Sprague-Dawley rats, to distinguish afferents, efferents, and vasculature. DNX kidneys and nondenervated kidneys were examined 1, 4, and 12 wk after DNX. Tissue levels of CGRP and norepinephrine (NE) were measured with ELISA and mass spectrometry, respectively. DNX decreased TH and CGRP labeling by 90% and 95%, respectively (P < 0.05) within 1 wk. After 12 wk TH and CGRP labeling returned to baseline with a shift toward afferent innervation (P < 0.05). Nondenervated kidneys showed a doubling of both labels within 12 wk (P < 0.05). CGRP content decreased by 72% [3.2 ± 0.3 vs. 0.9 ± 0.2 ng/gkidney; P < 0.05] and NA by 78% [1.1 ± 0.1 vs. 0.2 ± 0.1 pmol/mgkidney; P < 0.05] 1 wk after DNX. After 12 wk, CGRP, but not NE, content in DNX kidneys was fully recovered, with no changes in the nondenervated kidneys. The use of phenol in the DNX procedure did not influence this result. We found morphological reinnervation and transmitter recovery of afferents within 12 wk after DNX. Despite morphological evidence of sympathetic regrowth, NE content did not fully recover. These results suggest a long-term net surplus of afferent influence on the DNX kidney may be contributing to the blood pressure lowering effect of DNX.
EVALuna2:3840

COPEPTIN LEVELS IN PATIENTS WITH TREATMENT RESISTANT HYPERTENSION BEFORE AND AFTER RENAL DENERVATION - Jumar, A.; Ott, Christian; Schmid, Axel; Kannenkeril, Dennis; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2017)
EVALuna2:36267

Copeptin levels in patients with treatment resistant hypertension before and six months after renal denervation - Bosch, Agnes; Schmid, Axel; Ott, Christian; Kannenkeril, Dennis; Karg, Marina V.; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (American Journal of Hypertension, 2019)
BACKGROUND: Copeptin, the C-terminal peptide of pro-vasopressin, is released from the neurohypophysis and reflects the activity of the hormone arginine vasopressin in patients with hypertension. Elevated copeptin levels are associated with increased cardiovascular and all-cause mortality. The aim of this study is to compare copeptin levels in patients with treatment resistant hypertension (TRH) before and 6 months after renal denervation (RDN). METHODS: Copeptin was measured in 34 patients with TRH and 30 patients with primary hypertension stage 1 or 2 (HT). In addition, copeptin levels were measured in patients with TRH at 6 month follow-up visit after RDN. RDN was performed by an experienced interventionalist applying at least four ablations longitudinally and rotationally within the lengths of each renal artery to cover a full four quadrant ablation. RESULTS: In patients with TRH 24h ambulatory blood pressure (BP) decreased from 154±15/ 87±12 mmHg to 146±13/ 83±7.9 mmHg after RDN (systolic: p=0.001, diastolic: p=0.034). There was no significant change in copeptin levels in these 34 patients with TRH before versus six months after RDN (median 8.4 [interquartile range 3.6-14] vs 8.5 [4.5-13] pmol/l, p=0.334). Patients with TRH had higher copeptin levels (p=0.024) than patients with HT (24h ambulatory BP: 142±11/ 91±8.3 mmHg, copeptin: 4.2 [2.8-6.3] pmol/l). CONCLUSION: Patients with TRH showed 2 fold higher copeptin levels than patients with HT. RDN did not lead to any change of copeptin levels in patients with TRH 6 months after procedure despite significant fall in BP.
EVALuna2:210911

Dependency of flow-mediated vasodilatation from basal nitric oxide activity - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Jung, Susanne; Striepe, Kristina; Ott, Christian; Delles, Christian; Schmieder, Roland (Clinical Physiology and Functional Imaging, 2021)
Background: Flow-mediated vasodilatation (FMD) has become one of the most widely assessed parameters to analyse endothelial and vascular function in cardiovascular medicine. The degree of contribution of nitric oxide (NO) to FMD is inconclusive and varies widely depending on the device used. In this study, we used a semi-automatic ultrasound device to analyse to what extent basal NO activity contributes to FMD of the brachial artery. Methods: FMD was assessed with the UNEX EF device in a cross-over single blinded randomized study at baseline and then during infusion of either a NO-synthase-inhibitor (NG-monomethyl-L-arginine (L-NMMA)) or saline. The analysis was repeated after 1 week with the alternative infusion of L-NMMA or saline. All measurements were analysed both automatically and by a technician manually. Results: In total, 25 healthy men subjects completed the study. Diastolic blood pressure and heart rate significantly changed during infusion of L-NMMA. Infusion of L-NMMA reduced FMD significantly (−37%, p = 0.002). Saline solution had no effect on FMD (+14%, p = 0.392). Change in FMD was significantly different between the groups (ΔFMDL-NMMA vs. ΔFMDsaline, p = 0.032). There was a statistically significant correlation between automatically analysed results and those obtained by an experienced technician (FMDsaline: r = 0.822, p < 0.001; FMDL-NMMA: r = 0.645, p = 0.007). Conclusion: The influence of NO on FMD is approximately 40% if assessed using the UNEX EF. Prior to use FMD as a marker of endothelial dysfunction, we should explore different methods including various duration of forearm ischaemia to increase NO dependency of FMD.
CRIS-Team Scopus Importer:2021-04-02
Keywords: basal nitric oxide activity; flow-mediated vasodilatation; UNEX EF

Detection of Changes in Renal Blood Flow Using Arterial Spin Labeling MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (American Journal of Nephrology, 2021)
Background: Alteration in kidney perfusion is an early marker of renal damage. The purpose of this study was to evaluate if changes in renal blood flow (RBF) could be detected using MRI with arterial spin labeling (ASL) technique. Methods: RBF as assessed by cortical (CRBF), medullary, and total renal blood flow (TRBF) were measured by MRI with arterial spin labeling (ASL-MRI) using flow-sensitive alternating inversion recovery true fast imaging with steady-state precession sequence. In 11 normotensive healthy individuals (NT) and 11 hypertensive patients (HT), RBF was measured at baseline and after both feet were covered with cold ice packs (cold pressor test) that activates the sympathetic nervous system. In another experiment, RBF was measured in 10 patients with CKD before and after a pharmacological intervention. We compared RBF measurements between the 3 study populations. Results: A significant reduction in CRBF (p = 0.042) and a trend in TRBF (p = 0.053) were observed in response to the activation of the sympathetic nervous system. A trend toward reduction of CRBF (p = 0.051) and TRBF (p = 0.059) has been detected after pharmacological intervention. TRBF was significantly lower in patients with HT and CKD patients compared to NT individuals (NT vs. HT, p = 0.014; NT vs. CKD, p = 0.004). TRBF was lower in patients with CKD compared to HT (p = 0.047). Conclusion: Our data indicate that both acute and short-term changes in RBF could be detected using ASL-MRI. We were able to detect differences in RBF between healthy and diseased individuals by needing only small sample size per group. Thus, ASL-MRI offers an advantage in conducting clinical trials compared to other technologies.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ASL-MRI; Cold pressor test; Renal blood flow

DETECTION OF CHANGES IN RENAL BLOOD FLOW USING ARTERIAL SPIN LABELING MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Determinants of arterial stiffness in patients with type 2 diabetes mellitus: a cross sectional analysis - Staef, Mawadah; Ott, Christian; Kannenkeril, Dennis; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland; Bosch, Agnes (Scientific Reports, 2023)
In patients with type 2 diabetes mellitus (T2DM) arterial stiffness is associated with increased cardiovascular and total mortality. Little is known about determinants of arterial stiffness in clinical routine. Identification of potential determinants of arterial stiffness will help to address treatment targets for patients in the early state of T2DM. This is a cross-sectional analysis of arterial stiffness in 266 patients in the early stage of T2DM who did not have cardiovascular or renal complications. Parameters of arterial stiffness such as central systolic blood pressure (cSBP), central pulse pressure (cPP) and pulse wave velocity (PWV) were measured with the SphygmoCor System (AtCor Medical). We investigated the influence of parameters of glucose metabolism, lipid status, body constitution, blood pressure (BP) and inflammation on the stiffness parameters using multivariate regression analysis. The study cohort consisted of male and female patients aged 61 ± 8 years with mean diabetes duration of 6.4 ± 5.1 years, mean HbA1c 7.1 ± 0.9%, mean cSBP 121 ± 12 mmHg, mean cPP 44 ± 10 mmHg and mean PWV 8.9 ± 1.8 m/s. Multiple regression analysis identified waist circumference (WC) (beta = 0.411, p = 0.026), LDL-cholesterol (beta = 0.106, p = 0.006), systolic office BP (beta = 0.936, p < 0.001) and diabetes duration (beta = 0.233, p = 0.043) as potential determinants of cSBP. cPP was determined by sex (beta = 0.330, p = 0.008), age (beta = 0.383, p < 0.001), systolic office BP (beta = 0.370, p < 0.001) and diabetes duration (beta = 0.231, p = 0.028) whereas for PWV the following determinants could be identified: age (beta = 0.405, p < 0.001), systolic office BP (beta = 0.421, p < 0.001) and diabetes duration (beta = 0.073, p = 0.038). In addition to the known parameters age, sex and systolic office BP serum LDL-cholesterol, WC and diabetes duration have been identified as determinants of arterial stiffness in patients with T2DM. Treatment of patients in the early stage of T2DM should focus on these clinical parameters to prevent progression of arterial stiffness and as a consequence reduce cardiovascular mortality. Trial registration: The patients included in the analysis participated in one of the following clinical trials NCT02752113 (registered 26.4.2016), NCT02383238 (09.03.2015), NCT02471963 (15.06.2015), NCT01319357 (21.03.2011) (http://www.clinicaltrials.gov).
CRIS-Team Scopus Importer:2023-06-30

Diagnosis and treatment of arterial hypertension 2021 - Ott, Christian; Schmieder, Roland (Kidney International, 2021)
In the last 4 years, several evidence-based, national, and international guidelines on the management of arterial hypertension have been published, mostly with concordant recommendations, but in some aspects with discordant opinions. This in-depth review takes these guidelines into account but also addresses several new data of interest. Although being somewhat obvious and simple, accurate blood pressure (BP) measurement with validated devices is the cornerstone of the diagnosis of hypertension, but out-of-office BP measurements are of crucial importance as well. Simplified antihypertensive drug treatment such as single-pill combinations enhances the adherence to medication and speeds up the process of getting into the BP target range, a goal not so far adequately respected. Recommended (single-pill) combination therapy includes diuretics as part of the first step of antihypertensive therapy, and updated analysis does not provide evidence to exclude diuretics from this first step because of the recently discussed potential risk of increasing cancer incidence. Target BP goals need to be individualized, according to comorbidities, hypertension-mediated organ damage, coexistence of cardiovascular risk factors (including age), frailty in older patients, and individual tolerability. There are also concordant recommendations in the guidelines that an office BP between 120 and 140 mm Hg systolic and between 70 and 80 mm Hg diastolic should be achieved. The BP target of Kidney Disease: Improving Global Outcomes for hypertensive patients with chronic kidney disease are not applicable for clinical practice because they heavily rely on 1 study that used a study-specific, nontransferable BP measurement technique and excluded the most common cause of chronic kidney disease, namely, diabetic nephropathy. Actual data even from a prospective trial on chronotherapy have to be disregarded, and antihypertensive medication should not be routinely dosed at bedtime. Rigorously conducted trials justify the revival of renal denervation for treatment of (at least, but not only) uncontrolled and treatment-resistant hypertension.
CRIS-Team Scopus Importer:2021-12-17
Keywords: ambulatory blood pressure measurement; arterial hypertension; blood pressure; guideline; renal denervation; SPRINT

Difference in renal parenchymal perfusion after renal denervation comparing treated vs. non-treated arteries - Schmieder, R. S.; Schmid, Axel; Janka, Rolf Matthias; Schmieder, Roland; Ott, Christian; Uder, Michael (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

DIFFERENT FORMS OF AFFERENT NERVE INPUT IN CARDIAC AND RENAL DISEASE IN RATS? - Rodionova, Kristina; Ditting, Tilmann; Pickny, Lisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Disparate effects of the combined therapy of empagliflozin and linagliptin versus metformin and insulin glargine on renal haemodynamics in type 2 diabetes - Ott, Christian; Jung, Susan; Kannenkeril, Dennis; Striepe, Kristina; Bosch, Agnes; Korn, M.; Bramlage, P.; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

DISPARATE NITRIC OXIDE ACTIVITY OF THE RETINAL CIRCULATION IN HYPERTENSIVE VS TYPE 2 DIABETES-PATIENTS - Kannenkeril, Dennis; Jung, Susan; Harazny, J. M.; Bosch, Agnes; Ott, Christian; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Does renal artery supply indicate treatment success of renal denervation? - Schmid, Axel; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Schmieder, Roland; Uder, Michael; Ott, Christian (Cardiovascular and Interventional Radiology, 2013)
Purpose: Renal denervation (RDN) emerged as an innovative interventional antihypertensive therapy. With the exception of pretreatment blood pressure (BP) level, no other clear predictor for treatment efficacy is yet known. We analyzed whether the presence of multiple renal arteries has an impact on BP reduction after RDN. Methods: Fifty-three patients with treatment-resistant hypertension (office BP ≥ 140/90 mmHg and 24-h ambulatory BP monitoring (≥130/80 mmHg) underwent bilateral catheter-based RDN. Patients were stratified into one-vessel (OV) (both sides) and at least multivessel (MV) supply at one side. Both groups were treated on one vessel at each side; in case of multiple arteries, only the dominant artery was treated on each side. Results: Baseline clinical characteristics (including BP, age, and estimated glomerular filtration rate) did not differ between patients with OV (n = 32) and MV (n = 21). Office BP was significantly reduced in both groups at 3 months (systolic: OV -15 ± 23 vs. MV -16 ± 20 mmHg; diastolic: OV -10 ± 12 vs. MV -8 ± 11 mmHg, both p = NS) as well as 6 months (systolic: OV -18 ± 18 vs. MV -17 ± 22 mmHg; diastolic: OV -10 ± 10 vs. -10 ± 12 mmHg, both p = NS) after RDN. There was no difference in responder rate (rate of patients with office systolic BP reduction of at least 10 mmHg after 6 months) between the groups. Conclusion: In patients with multiple renal arteries, RDN of one renal artery - namely, the dominant one - is sufficient to induce BP reduction in treatment-resistant hypertension. © 2013 Springer Science+Business Media New York and the Cardiovascular and Interventional Radiological Society of Europe (CIRSE).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Ablation; Artery; Endovascular treatment; Hypertension; Kidney/renal; Radiofrequency ablation

Early Signs of End-Organ Damage in Retinal Arterioles in Patients with Type 2 Diabetes Compared to Hypertensive Patients - Jumar, Agnes; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Michelson, Georg; Harazny, Joanna M.; Schmieder, Roland (Microcirculation, 2016)
Eutrophic and hypertrophic remodeling are major vascular hallmarks for hypertension and diabetes-associated microvascular end-organ damage in peripheral arterioles. The aim of this study is to compare retinal arterioles of diabetic, hypertensive, and healthy individuals.Retinal parameters were assessed in 99 patients with T2DM, 158 hypertensive, and 149 healthy individuals. WT and CA of retinal arterioles (80-140 ?m) were measured noninvasively and in vivo by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany).After adjustment for values differing between the groups (age, BMI, gender, HDL cholesterol and serum creatinine, systolic office BP), patients with T2DM showed no significant difference in WT (14.2 ± 3), and CA (4199 ± 1107) in comparison with hypertensive patients (WT = 13.3 ± 4, p = 0.18, CA = 3862 ± 1546, p = 0.10) and healthy individuals (WT = 13.1 ± 3, p = 0.55, CA = 3864 ± 1216, p = 0.86). However, the subgroup of patients with diabetes duration of more than 60 months showed greater WT (14.9 ± 4, p = 0.04) and CA (4557 ± 1137, p = 0.02) than the hypertensive group and greater WT (p = 0.04) and CA (p = 0.03) than the healthy group, which is consistent with hypertrophic remodeling.In the early stage of T2DM no hypertrophic remodeling was seen in retinal arterioles. However, hypertrophic remodeling was found in diabetic patients with more than 60 months duration of disease.
EVALuna2:3870

Early vascular parameters in the micro- and macrocirculation in type 2 diabetes - Kannenkeril, Dennis; Bosch, Agnes; Harazny, Joanna; Karg, Marina; Jung, Susan; Ott, Christian; Schmieder, Roland (Cardiovascular Diabetology, 2018)
BACKGROUND: Diabetes converts from a metabolic disorder into a predominantly vascular disease, once its duration extends over several years or/and when additional cardiovascular risk factors such as hypertension coexist. In a cross-sectional analysis we analyzed various vascular parameters in the renal, retinal and systemic circulation, with the goal to identify which vascular parameter of early organ damage is the earliest that can be clinically detected. METHODS: In 111 patients with type 2 diabetes (T2DM) (off any anti-diabetic medication for at least 4 weeks) and 54 subjects without T2DM we compared various parameters of early vascular remodeling in the same patient: urinary albumin creatinine ratio ([UACR], early morning spot urine) and estimated glomerular filtration rate (eGFR), retinal capillary flow (RCF) and intercapillary distance (ICD) as parameters of capillary rarefaction, wall-to-lumen ratio (WLR) of the retinal arterioles [all assessed by Scanning Laser Doppler Flowmetry], and central systolic pressure (cSBP) and central pulse pressure (cPP) [measured by pulse wave analysis, Syphygmocor] both reflecting vascular stiffness of large arteries. RESULTS: Compared to subjects without T2DM, patients with T2DM (diabetes duration: median 48 months, interquartile range 24-88 months) were older (59.8 ± 7.3 vs 43.4 ± 12.9 years, p < 0.001), more females (33.3 vs 20.4%, p < 0.001), but 24-h systolic and diastolic blood pressure did not differ between the two groups. The analysis adjusted for age, gender and cardiovascular risk factors revealed that ICD (23.9 ± 5.1 vs 20.8 ± 3.5 µm, p value = 0.001) and cPP (41.8 ± 11.7 vs 34.8 ± 10.6 mmHg, p value < 0.001) were significantly higher and eGFR (91.7 ± 9.9 vs 95.9 ± 17.3 ml/min/1.73 m2, p value < 0.001) was significantly lower in patients with T2DM than in subjects without T2DM. CONCLUSION: These data suggest that at similar blood pressure capillary rarefaction in the retinal circulation (ICD), decreased eGFR in the renal circulation and increased central pulse pressure (cPP) of large arteries are earlier detectable than other vascular remodeling parameters of the micro- (WLR, RCF, UACR) and macrocirculation (cSBP) in patients with T2DM. Trial registration Trial registration number: NCT02471963, Date of registration: June 15, 2015, retrospectively registered; Trial registration number: NCT01319357, Date of registration: March 21, 2011, retrospectively registered; Trial registration number: NCT02383238, Date of registration: March 9, 2015, retrospectively registered; Trial registration number: NCT00152698, Date of registration: September 9, 2005, prospectively registered; Trial registration number: NCT00136188, Date of registration: August 26, 2005, prospectively registered.
EVALuna2:35230

Effect of aliskiren on vascular remodelling in small retinal circulation - Jumar, Agnes; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Schmidt, Stefan; Harazny, Joanna M.; Schmieder, Roland (Journal of Hypertension, 2015)
In hypertension, changes in small arterial structure are characterized by an increased wall-to-lumen ratio (WLR). These adaptive processes are modulated by the rennin-angiotensin system. It is unclear whether direct renin inhibitors exert protective effects on small arteries in hypertensive patients.In this double-blind, randomized, placebo-controlled study (http://www.clinicaltrials.gov: NCT01318395), 114 patients with primary hypertension were randomized to additional therapy with either placebo or aliskiren 300 mg for 8 weeks after 4 weeks of standardized open-label treatment with valsartan 320 mg (run-in phase). Parameter of arteriolar remodelling was WLR of retinal arterioles (80 - 140 ?m) assessed noninvasively and in vivo by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany). In addition, pulse wave analysis (SphygmoCor, AtCor Medical, Australia) and pulse pressure (PP) amplification were determined.In the whole study population, no clear effect of additional therapy with aliskiren on vascular parameters was documented. When analyses were restricted to patients with vascular remodelling, defined by a median of WLR more than 0.3326 (n = 57), WLR was reduced after 8 weeks by the treatment with aliskiren compared with placebo (-0.044 ± 0.07 versus 0.0043 ± 0.07, P = 0.015). Consistently, after 8 weeks of on-top treatment with aliskiren, there was an improvement of PP amplification compared with placebo (0.025 ± 0.07 versus -0.034 ± 0.08, P = 0.013), indicative of less stiff arteries in the peripheral circulation.Thus, our data indicate that treatment with aliskiren, given on top of valsartan therapy, improves altered vascular remodelling in hypertensive patients.
EVALuna2:3799

Effect of Arteriovenous Anastomosis on Blood Pressure Reduction in Patients With Isolated Systolic Hypertension Compared With Combined Hypertension - Ott, Christian; Lobo, Melvin D.; Sobotka, Paul A.; Mahfoud, Felix; Stanton, Alice; Cockcroft, John; Sulke, Neil; Dolan, Eamon; Van Der Giet, Markus; Hoyer, Joachim; Furniss, Stephen S.; Foran, John P.; et al. (Journal of the American Heart Association, 2016)
Options for interventional therapy to lower blood pressure (BP) in patients with treatment-resistant hypertension include renal denervation and the creation of an arteriovenous anastomosis using the ROX coupler. It has been shown that BP response after renal denervation is greater in patients with combined hypertension (CH) than in patients with isolated systolic hypertension (ISH). We analyzed the effect of ROX coupler implantation in patients with CH as compared with ISH.The randomized, controlled, prospective ROX Control Hypertension Study included patients with true treatment-resistant hypertension (office systolic BP >=140 mm Hg, average daytime ambulatory BP >=135/85 mm Hg, and treatment with >=3 antihypertensive drugs including a diuretic). In a post hoc analysis, we stratified patients with CH (n=31) and ISH (n=11). Baseline office systolic BP (177±18 mm Hg versus 169±17 mm Hg, P=0.163) and 24-hour ambulatory systolic BP (159±16 mm Hg versus 154±11 mm Hg, P=0.463) did not differ between patients with CH and those with ISH. ROX coupler implementation resulted in a significant reduction in office systolic BP (CH: -29±21 mm Hg versus ISH: -22±31 mm Hg, P=0.445) and 24-hour ambulatory systolic BP (CH: -14±20 mm Hg versus ISH: -13±15 mm Hg, P=0.672), without significant differences between the two groups. The responder rate (office systolic BP reduction >=10 mm Hg) after 6 months was not different (CH: 81% versus ISH: 82%, P=0.932).Our data suggest that creation of an arteriovenous anastomosis using the ROX coupler system leads to a similar reduction of office and 24-hour ambulatory systolic BP in patients with combined and isolated systolic hypertension.URL: http://www.clinicaltrials.gov. Unique identifier: NCT01642498.
EVALuna2:3926

Effects of folic acid on renal endothelial function in patients with diabetic nephropathy: results from a randomized trial - Schneider, Markus P.; Schneidert, Andreas; Jumar, Agnes; Kistner, Iris; Ott, Christian; Schmieder, Roland (Clinical Science, 2014)
Endothelial dysfunction has been shown to promote podocyte injury and albuminuria in diabetes, highlighting the importance of the interaction between renal endothelial cells and podocytes. Folic acid (FA) improves nitric oxide synthase (NOS) function and reduces progression of diabetic nephropathy in animal models. We tested whether high-dose FA treatment improves renal endothelial function and albuminuria in human subjects with incipient diabetic nephropathy. Following a double-blind, randomized, cross-over design, 28 patients with Type 2 diabetes and albuminuria were allocated to 4 weeks' treatment with placebo and high-dose FA (5 mg/day). Renal nitric oxide (NO) production determined as the response of renal plasma flow (RPF) to NOS inhibition with NG-monomethyl-L-arginine (L-NMMA) (4.25 mg/kg intravenously), renal oxidant stress as response of RPF to vitamin C infusion (3 mg/kg) and albuminuria were determined after each treatment phase. Neither the reduction in RPF to L-NMMA nor the increase in RPF to vitamin C infusion differed between treatment phases (?RPF to L-NMMA: -74±71 ml/min per m2 during placebo compared with -63±56 ml/min per m2 during FA, P=0.57; ?RPF to vitamin C: +93±118 ml/min per m2 compared with +94±108 ml/min per m2; P=0.70). In line with the lack of effect on the renal endothelium, albuminuria was not affected by FA treatment (110±179 mg/day during placebo compared with 87±146 mg/day during FA; P=0.12). High-dose FA treatment does not improve renal endothelial function and fails to reduce albuminuria in human subjects with diabetic nephropathy. Novel treatment options for oxidant stress and endothelial dysfunction in patients with diabetes are urgently needed.
EVALuna2:3679

Effects of linagliptin on renal endothelial function in patients with type 2 diabetes: a randomised clinical trial - Ott, Christian; Kistner, Iris; Keller, Mirjam; Friedrich, Stefanie; Willam, Carsten; Bramlage, Peter; Schmieder, Roland (Diabetologia, 2016)
Endothelial dysfunction predicts cardiovascular damage and renal involvement. Animal experiments and human studies indicate an increased nitric oxide (NO) activity and endothelial NO synthase (NOS) expression in the early stage of type 2 diabetes. The aim of the study was to assess the effect of linagliptin on the endothelial function of the renal vasculature.In this randomised, double-blind, parallel-group, investigator-initiated trial, 62 patients with type 2 diabetes were randomly assigned (by computer-generated random code) to receive linagliptin 5 mg (n = 30) or placebo (n = 32) for 4 weeks. The primary objective was to assess endothelial function of the renal vasculature, by constant-infusion input-clearance and urinary albumin/creatinine ratio (UACR), both before and after blockade of NOS with N (G)-monomethyl-L-arginine (L-NMMA).Treatment with linagliptin for 4 weeks reduced fasting, postprandial blood glucose and HbA1c, although not significantly; no change occurred with placebo. Renal plasma flow (RPF) did not change after linagliptin or placebo. After 4 weeks the absolute change in RPF due to L-NMMA was smaller in the linagliptin group than in the placebo group (-46.8 ± 34 vs -65.1 ± 36 ml/min, p = 0.045), indicating a lower basal NO activity after treatment with linagliptin. Consistently, the response of UACR to L-NMMA increased in the placebo group (p = 0.059) but not in the linagliptin group (p = 0.276), pointing to an upregulation of NO activity in the placebo group. No clinically meaningful safety concerns were evident.Our data suggest that treatment with the dipeptidyl peptidase-4 inhibitor linagliptin for 4 weeks prevented the impairment of renal endothelial function due to hyperglycaemia in type 2 diabetes.ClinicalTrials.gov NCT01835678 FUNDING: : This study was funded by Boehringer Ingelheim.
EVALuna2:3903

EFFECTS OF NEUROGENIC CGRP ON RENAL AFFERENT PEPTIDERGIC NEURONS - Veelken, Roland; Raschke, Giulia; Ditting, Tilmann; Ott, Christian; Schmieder, Roland; Amann, Kerstin Ute; Rodionova, Kristina (2018)
EVALuna2:204843

EFFECTS OF RENAL DENERVATION IN PATIENTS WITH VERSUS WITHOUT CHRONIC KIDNEY DISEASE: UPDATED DATA FROM THE GLOBAL SYMPLICITY REGISTRY WITH FOLLOW-UP OF 3 YEARS - Ott, Christian; Mahfoud, F.; Mancia, G.; Narkiewicz, K.; Ruilope, L. M.; Schlaich, M. P.; Williams, B.; Boehm, M.; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Effects of renal denervation on blood pressure in hypertensive patients with end-stage renal disease: a single centre experience - Ott, Christian; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (Clinical and Experimental Nephrology, 2019)
Background: Sympathetic nerve activity is a hallmark of hypertension in end-stage renal disease (ESRD). An initial proof-of-concept study implies that renal denervation (RDN) is feasible and safe in RDN, but overall data are limited. Methods: In this single-centre prospective pilot study six patients with ESRD and treatment resistant hypertension were consecutively included. Ambulatory blood pressure (ABP) was measured before and 6 months after RDN (Symplictiy Flex™, Medtronic Inc., Santa Rosa, CA). Moreover, haemodialysis parameters which may affect BP reduction were monitored closely. Results: In all patients bilateral RDN was successful done, without documentation of peri- or postprocedural complications. There was a significant reduction in 24-h ABP by 20 ± 17/15 ± 12 mmHg 6 months after RDN (systolic: 163 ± 16 versus 143 ± 9 mmHg, p = 0.043; diastolic: 96 ± 9 versus 81 ± 15 mmHg, p = 0.043), with similar results for day-, and nighttime values, respectively. Antihypertensive medication was kept stable as well as there was no change in haemodialysis parameters during follow-up. In addition, ultrafiltration/week (1.4 ± 1.4 versus 2.2 ± 1.4 l, p = 0.08) as well as hematocrit (measured at baseline and 6 months after RDN) (33.7 ± 4.3 versus 33.1 ± 3.9%, p = 0.715) revealed no change in volume status. Conclusion: Our single-centre pilot study not only supports current data on renal safety of RDN even in small arteries of patients with ESRD, but also enhances the knowledge towards an effective ABP reduction in this type of hypertensive patients.
CRIS-Team Scopus Importer:2019-05-07
Keywords: End-stage renal disease; Renal denervation; Treatment resistant hypertension

Effects of renal sympathetic denervation on urinary sodium excretion in patients with resistant hypertension - Poss, Janine; Ewen, Sebastian; Schmieder, Roland; Muhler, Sonja; Vonend, Oliver; Ott, Christian; Linz, Dominik; Geisel, Juergen; Rump, Lars C.; Schlaich, Markus; Boehm, Michael; Mahfoud, Felix (Clinical Research in Cardiology, 2015)
Sympathetic overactivity increases sodium retention and contributes to the pathophysiology of hypertension. Renal sympathetic denervation lowers blood pressure and reduces sympathetic activity in certain patients with resistant hypertension.This study aimed to assess the effect of renal denervation on urinary sodium excretion. 24-h urinary sodium excretion was estimated at baseline and after 6 months using the Kawasaki formula in 137 patients with resistant hypertension undergoing renal denervation. Sodium excretion was adjusted for cystatin C GFR and fractional sodium excretion was assessed. Mean office systolic blood pressure at baseline was 171 ± 2 mmHg despite an intake of 5.2 ± 0.1 antihypertensive drugs. Six months after renal denervation, systolic and diastolic BP decreased by 18 ± 2 mmHg (p < 0.0001) and 10 ± 1 mmHg (p < 0.001). 90 patients (65.7 %) had SBP reductions >=10 mmHg (responders). After 6 months, 24-h UNa increased by 13 % compared to baseline (236 ± 9 vs. 268 ± 9 mmol/day, p < 0.003). This increase was most pronounced in patients with less response in BP. These findings were paralleled by a significant increase in fractional sodium excretion (1.19 ± 0.11 vs. 1.64 ± 0.14 %, p < 0.0001) and were observed independently of the intake of antihypertensive drugs affecting sodium balance, such as mineralocorticoid receptor antagonists or diuretics.RDN lowered BP and increased estimated UNa and fractional sodium excretion in patients with resistant hypertension independently of renal function and antihypertensive therapy.
EVALuna2:3761

Effects of saxagliptin on early microvascular changes in patients with type 2 diabetes - Ott, Christian; Raff, Ulrike; Schmidt, Stefan; Kistner, Iris; Friedrich, Stefanie; Bramlage, Peter; Harazny, Joanna M.; Schmieder, Roland (Cardiovascular Diabetology, 2014)
Patients with diabetes mellitus are at increased risk for microvascular complications. Early changes in microcirculation are characterized by hyperperfusion (e.g. in the retina and kidney) and increased pulse wave reflection leading to increased aortic pressure. We investigated the effects of the DPP-4-inhibitor saxagliptin on early retinal microvascular changes.In this double-blind, controlled, cross-over trial 50 patients (without clinical signs of microvascular alterations) with type-2 diabetes (mean duration of 4 years) were randomized to receive placebo or 5 mg saxagliptin for 6 weeks. Retinal arteriolar structure and retinal capillary flow (RCF) at baseline and during flicker-light exposure was assessed by scanning laser Doppler flowmetry. Central hemodynamics were assessed by pulse wave analysis.Postprandial blood glucose (9.27 ± 0.4 versus 10.1 ± 0.4 mmol/L; p = 0.001) and HbA1c (6.84 ± 0.15 (51 ± 1.6) versus 7.10 ± 0.17% (54 ± 1.9 mmol/mol); p < 0.001) were significantly reduced with saxagliptin treatment compared to placebo. RCF was significantly reduced after treatment with saxagliptin (288 ± 13.2 versus 314 ± 14.1 AU; p = 0.033). This was most pronounced in a subgroup of patients (n = 32) with a fall in postprandial blood glucose (280 ± 12.1 versus 314 ± 16.6 AU; p = 0.011). No significant changes in RCF were seen during flicker-light exposure between placebo and saxagliptin, but the vasodilatory capacity increased two-fold with saxagliptin treatment. Central augmentation pressure tended to be lower after treatment with saxagliptin (p = 0.094), and central systolic blood pressure was significantly reduced (119 ± 2.3 versus 124 ± 2.3 mmHg; p = 0.038).Our data suggest that treatment with saxagliptin for 6 weeks normalizes retinal capillary flow and improves central hemodynamics in type-2 diabetes.The study was registered at (ID: NCT01319357).
EVALuna2:3676

Effects of the nitric oxide synthase inhibitor ronopterin (VAS203) on renal function in healthy volunteers - Ott, Christian; Bosch, Agnes; Winzer, Nicole; Friedrich, Stephanie; Schinzel, Reinhard; Tegtmeier, Frank; Schmieder, Roland (British Journal of Clinical Pharmacology, 2019)
Aims: Reduced nitric oxide (NO) availability may adversely affect renal perfusion and glomerular filtration. The aim of the present study was to characterize in detail the pharmacological effects of VAS203, an inhibitor of NO synthase, on renal haemodynamics in humans. Methods: This double-blind, randomized, placebo-controlled, cross-over phase-I-study comprised 18 healthy men. Renal haemodynamics were assessed with constant-infusion input-clearance technique with p-aminohippurate and inulin for renal plasma flow (RPF) and glomerular filtration rate (GFR), respectively. After baseline measurement, a constant infusion of the tetrahydrobiopterin analogue ronopterin (VAS203, total 10 mg/kg body weight) or placebo was administered at random order for 6 hours additionally. After a wash-out phase of 28 days, the second course was applied. In parallel, markers of early kidney injury and renal function were assessed repeatedly up to 48 hours after starting VAS203/placebo-infusion. Results: VAS203-infusion resulted in a significant decrease of RPF (P <.0001) and GFR (P <.001) compared to placebo, but magnitude was within the physiological range. RPF and GFR recovered partly 2 hours after end of VAS203-infusion and was normal at beginning of the second infusion period. Compared to placebo, preglomerular resistance (P <.0001), and to lesser extent postglomerular resistance (P <.0001) increased, resulting in a decrease of intraglomerular pressure (P <.01). No treatment related effect on markers of early kidney injury, and on renal function (P for all >.20) have been observed. Conclusions: Our phase-I-study in healthy humans indicates that VAS203 (10 mg/kg body weight) reduces renal perfusion and glomerular function within the physiological range mainly due to vasoconstriction at the preglomerular site.
CRIS-Team Scopus Importer:2019-05-03
Keywords: glomerular filtration rate; nitric oxide synthase; renal haemodynamics; renal plasma flow; VAS203

EFFECTS OF THE NO SYNTHASE INHIBITOR RONOPTERIN (VAS203) ON MICRO- AND MACROCIRCULATION IN HEALTHY VOLUNTEERS - Ott, Christian; Bosch, Agnes; Jung, Susan; Kannenkeril, Dennis; Schinzel, R.; Tegtmeier, F.; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Effects of the Selective Sodium-Glucose Cotransporter 2 Inhibitor Empagliflozin on Vascular Function and Central Hemodynamics in Patients With Type 2 Diabetes Mellitus - Striepe, Kristina; Jumar, Agnes; Ott, Christian; Karg, Margarete; Schneider, Markus; Kannenkeril, Dennis; Schmieder, Roland (Circulation, 2017)
EVALuna2:4021

EFFECTS OF THE SGLT2 INHIBITOR EMPAGLIFLOZIN ON VASCULAR FUNCTION IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Bosch, Agnes; Jung, Susanne; Linz, Peter; Kannenkeril, Dennis; Nagel, Armin Michael; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

Effects of the sodium-glucose cotransporter 2 inhibitor empagliflozin on vascular function in patients with chronic heart failure - Kolwelter, Julie; Bosch, Agnes; Jung, Susanne; Stabel, Lena; Kannenkeril, Dennis; Ott, Christian; Bramlage, Peter; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims Impairment of vascular function contributes to the progression of chronic heart failure (HF) by increasing the afterload. Treatment with selective sodium-glucose cotransporter 2 (SGLT2) inhibitors improves the prognosis of HF, but the precise mechanisms remain unclear. The aim of this study was to analyse the effect of empagliflozin on vascular function in patients with HF.
CRIS-Team WoS Importer:2021-10-01

European Society of Hypertension position paper on renal denervation 2018 - Schmieder, Roland; Mahfoud, Felix; Azizi, Michel; Pathak, Atul; Dimitriadis, Kyriakos; Kroon, Abraham A.; Ott, Christian; Scalise, Filippo; Mancia, Giuseppe; Tsioufis, Costas (Journal of Hypertension, 2018)
: This ESH update was deemed necessary with the publication of new results of sham-controlled randomized blinded prospective trials with renal denervation (RDN). Proof of concept studies and first randomized trials (some were sham-controlled) displayed discrepant results about the efficacy of RDN. Three sham-controlled randomized trials of the 2.0 generation yielded now similarity in the average blood pressure decrease following RDN. Reduction of ambulatory blood pressure was approximately 5 to 7 mmHg and of office blood pressure 10 mmHg. Such a decrease in blood pressure by pharmacologic therapy has been found to be associated with lower incidence of cardiovascular events in particular with respect to heart failure and stroke by roughly 25%. Nevertheless, some questions about renal denervation are unanswered. The heterogeneity of the blood pressure-lowering response point to the clinical need to identify predictors for efficacy, and questions on long-term safety could not have been answered due to the short duration of the sham-controlled randomized clinical trials.
EVALuna2:34507

Evidence of neurodegeneration in individuals with only mildly elevated blood pressure - Jung, Susanne; Bosch, Agnes; Kohler, Nikolas; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2019)
OBJECTIVE: Initiation of antihypertensive drug treatment in low-risk individuals with grade 1 hypertension is under debate. The aim of this study was to examine the impact of mildly elevated blood pressure (BP) on early neurodegenerative processes independent of ageing. METHODS: Sixty-two individuals were included in this study: 25 young (aged <40 years) and 37 older (aged ≥40 years) individuals at low cardiovascular risk and grade 1 hypertension at most. Macular retinal layer volumes of both eyes were determined by SD-OCT. Total retinal volume but also each inner retinal layer volume separately including retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), and GCL-IPL were measured in each individual. RESULTS: Retinal layer volumes were lower among older individuals compared with young individuals (RNFL right eye: P = 0.037/left eye: P = 0.021; GCL and GCL-IPL: both eyes P < 0.001; IPL right eye: P = 0.005/left eye: P = 0.002; total retinal volume: both eyes P = 0.002) and there was an inverse correlation between retinal layer volumes and age. Partial correlation analysis, excluding age as a cofactor, revealed an inverse association between retinal layer volumes and DBP. In multiple regression analysis, DBP was identified as a determinant of retinal neurodegenerative processes. CONCLUSION: In the current study, we observed an inverse association between retinal neurodegenerative processes and DBP, suggesting that BP-lowering therapy by early antihypertensive drug-treatment might be beneficial to avoid early neurodegeneration.
EVALuna2:203883

First experience in analysing pulsatile retinal capillary flow and arteriolar structural parameters measured noninvasively in hypertensive patients - Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Welzenbach, Juergen; Kwella, Norbert; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2014)
Increased pulsatile pressure induces as well as aggravates microvascular damage. Scanning laser Doppler flowmetry allows the noninvasive assessment of both retinal capillary flow (RCF) and arteriolar structural parameters of the retinal circulation. Moreover, pulsatile characteristics of the retinal arterioles can be assessed.In study 1, reliability of pulsatile RCF and structural parameters were examined in randomly selected patients. In study 2, pulsatile RCF as well as the structural parameters of retinal arterioles were assessed in hypertension grade 1-2 (HT1-2; n = 20) and treatment-resistant hypertension (TRH; n = 19).In study 1, test-retest, interobserver and intraobserver reliability of all parameters showed coefficients of variation of less than 10%. In study 2, it was shown that patients with TRH had higher pulse pressure (P = 0.003) and pulsed RCF values (P < 0.001) as patients with HT1-2. Patients with HT1-2 had no change in the vessel diameter, but a significant difference in lumen diameter, resulting in an altered wall thickness (P = 0.001) between systole and diastole. In contrast, patients with TRH showed differences in vessel diameter (P = 0.005) as well as lumen diameter (P = 0.001), resulting in an unaltered wall thickness between systole and diastole. Hence, wall thickness change as a result of pulsed flow regulation observed in HT1-2 was missing in TRH.We suggest a new reliable tool for evaluating the pulsatility in the retinal circulation in humans, and found significant differences in pulsatile RCF and structural parameters between patients with HT1-2 and those with TRH.
EVALuna2:3718

FLOW MEDIATED VASODILATION/VASOCONSTRICTION IN DIFFERENT DISEASE POPULATIONS - Kannenkeril, Dennis; Dienemann, T.; Jung, Susan; Striepe, Kristina; Kopp, C.; Schneider, M.; Ott, Christian; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Haemoglobin and vascular function in the human retinal vascular bed - Ritt, Martin; Harazny, Joanna M.; Schmidt, Stefan; Raff, Ulrike; Ott, Christian; Michelson, Georg; Schmieder, Roland (Journal of Hypertension, 2013)
: Haemoglobin is a potential nitric oxide (NO) scavenger. Haemoglobin is associated with blood viscosity and the red blood cell free layer width of microvessels that impact on shear stress in the microcirculation. We hypothesized that haemoglobin modulates retinal vascular function.: In 139 nondiabetic male patients with haemoglobin levels within the normal range, the vasodilatatory response of retinal capillary blood flow (RCF) to flicker light exposure and the vasoconstrictor response of RCF to infusion of NO synthase inhibitor N-monomethyl-L-arginine (L-NMMA) were assessed. The latter, because of the selective nature of L-NMMA, reflects a parameter of basal NO activity of retinal vasculature. Examinations of retinal parameters were performed noninvasively and in vivo using scanning laser Doppler flowmetry.: Patients with haemoglobin greater or equal the median revealed reduced increase of RCF to flicker light exposure (2.83 ± 12 vs. 9.52 ± 14 (%), P adjusted = 0.002), and greater decrease of RCF to L-NMMA infusion (-7.35 ± 13 vs. -0.92 ± 14 (%), P adjusted = 0.008), compared with patients with haemoglobin below the median. Haemoglobin was negatively related to the percentage change of RCF to flicker light exposure (r = -0.249, P = 0.004) and to L-NMMA infusion (r = -0.201, P = 0.018). In multiple linear regression analysis haemoglobin was an independent determinant of the percentage change of RCF to flicker light exposure (model 1: ß = -0.278, P = 0.003 and model 2: ß = -0.283, P = 0.002) and to L-NMMA infusion (model 1: ß = -0.256, P = 0.005 and model 2: ß = -0.269, P = 0.004).: Haemoglobin emerged as an independent determinant of vascular function in the human retinal vascular bed.
EVALuna2:3613

High Sodium Diet - Role in Renal Sympathodepression - Rodionova, Kristina; Ditting, Tilmann; Fahrmeier, Franziska; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland (FASEB JOURNAL, 2020)
CRIS-Team WoS Importer:2020-10-16

How does empagliflozin improve arterial stiffness in patients with type 2 diabetes mellitus? - Bosch, A.; Ott, Christian; Jung, Susan; Striepe, Kristina; Karg, M. V.; Kannenkeril, Dennis; Dienemann, T.; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

How does empagliflozin improve arterial stiffness in patients with type 2 diabetes mellitus? Sub analysis of a clinical trial - Bosch, Agnes; Ott, Christian; Jung, Susan; Striepe, Kristina; Karg, Marina V.; Kannenkeril, Dennis; Dienemann, Thomas; Schmieder, Roland (Cardiovascular Diabetology, 2019)
BackgroundEmpagliflozin has been shown to reduce cardiovascular mortality, but the underlying pathogenetic mechanisms are poorly understood. It was previously demonstrated that empagliflozin improved arterial stiffness.MethodsOur analysis comprising 58 patients with type 2 diabetes mellitus identifies factors triggering the improvement of arterial stiffness. All patients participated in an investigator-initiated, prospective, double-blind, randomized, placebo-controlled, interventional clinical trial (http://www.ClinicalTrials.gov: NCT02471963, registered 15th June 2015, retrospectively registered) and received either 6-weeks treatment with 25mg empagliflozin orally once daily or placebo (crossover). Central systolic pressure and central pulse pressure were recorded by the SphygmoCor System (AtCor Medical). Now, we investigated the impact of parameters of glucose metabolism, volume status, sympathetic activation, lipids, uric acid, blood pressure and inflammation on vascular parameters of arterial stiffness using multivariate regression analysis.ResultsAs previously reported, therapy with empagliflozin improved arterial stiffness as indicated by reduced central systolic blood pressure (113.612.1 vs 118.612.9mmHg, p<0.001), central pulse pressure (39.1 +/- 10.2 vs 41.9 +/- 10.7mmHg, p=0.027) forward (27.1 +/- 5.69 vs 28.7 +/- 6.23mmHg, p=0.031) as well as reflected wave amplitude (18.9 +/- 5.98 vs 20.3 +/- 5.97mmHg, p=0.045) compared to placebo. The multivariate regression analysis included age, sex and change between empagliflozin and placebo therapy of the following parameters: HbA1c, copeptin, hematocrit, heart rate, LDL-cholesterol, uric acid, systolic 24-h ambulatory blood pressure and high sensitive CRP (hsCRP). Besides the influence of age (beta=-0.259, p=0.054), sex (beta=0.292, p=0.040) and change in systolic 24-h ambulatory blood pressure (beta=0.364, p=0.019), the change of hsCRP (beta=0.305, p=0.033) emerged as a significant determinant of the empagliflozin induced reduction in arterial stiffness (placebo corrected). When replacing HbA1c with fasting plasma glucose in the multivariate regression analysis, a similar effect of the change in hsCRP (beta=0.347, p=0.017) on arterial stiffness parameters was found.Conclusion Besides age and sex, change in systolic 24-h ambulatory blood pressure and change in hsCRP were determinants of the empagliflozin induced improvement of vascular parameters of arterial stiffness, whereas parameters of change in glucose metabolism and volume status had no significant influence. Our analysis suggests that empagliflozin exerts, at least to some extent, its beneficial vascular effects via anti-inflammatory mechanisms.
CRIS-Team WoS Importer:2019-04-18

Hypertrophic remodelling of retinal arterioles in patients with congestive heart failure - Jung, Susanne; Kolwelter, Julie; Bosch, Agnes; Cífková, Renata; Harazny, Joanna M.; Ott, Christian; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims: Analysis of microvascular parameters in the retinal circulation—known to reflect those in the systemic circulation—allows us to differentiate between eutrophic and hypertrophic remodelling of small arteries. This study aimed to examine microvascular changes in patients with congestive heart failure (CHF) and reduced as well as mid-range ejection fraction. Methods and results: Forty subjects with CHF underwent measurement of retinal capillary flow (RCF), wall-to-lumen ratio (WLR), vessel and lumen diameter, wall thickness, and wall cross-sectional area (WCSA) of retinal arterioles of the right eye by scanning laser Doppler flowmetry (SLDF). Applying a matched pair approach, we compared this group with reference values of age-matched controls from a random sample in the population of Pilsen, Czech Republic. There was no significant difference in RCF and WLR between the groups (RCF: P = 0.513; WLR: P = 0.106). In contrast, wall thickness and WCSA, indicators of hypertrophic remodelling, were higher in CHF subjects (WT: 15.0 ± 4.2 vs. 12.7 ± 4.2 μm, P = 0.021; WCSA: 4437.6 ± 1314.5 vs. 3615.9 ± 1567.8 μm2, P = 0.014). Similarly, vessel (109.4 ± 11.1 vs. 100.5 ± 14.4 μm, P = 0.002) and lumen diameter (79.0 ± 7.9 vs. 75.2 ± 8.5 μm, P = 0.009) were increased in CHF. Conclusions: In CHF subjects, we observed hypertrophic remodelling of retinal arterioles indicative of similar changes of small resistance arteries in the systemic circulation. Microvascular structure and function assessed by SLDF may thereby represent a useful, non-invasive method for monitoring of microvascular damage in patients with CHF and may offer innovative treatment targets for new CHF therapies.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Heart failure; Hypertrophic remodelling; Microvasculature; Retina

Identifying Isolated Systolic Hypertension From Upper-Arm Cuff Blood Pressure Compared With Invasive Measurements - Picone, Dean S.; Schultz, Martin G.; Armstrong, Matthew K.; Black, J. Andrew; Bos, Willem Jan W.; Chen, Chen Huan; Cheng, Hao Min; Cremer, Antoine; Dwyer, Nathan; Hughes, Alun D.; Kim, Hack Lyoung; Lacy, Peter S.; et al. (Hypertension, 2021)
Isolated systolic hypertension (ISH) is the most common form of hypertension and is highly prevalent in older people. We recently showed differences between upper-arm cuff and invasive blood pressure (BP) become greater with increasing age, which could influence correct identification of ISH. This study sought to determine the difference between identification of ISH by cuff BP compared with invasive BP. Cuff BP and invasive aortic BP were measured in 1695 subjects (median 64 years, interquartile range [55-72], 68% male) from the INSPECT (Invasive Blood Pressure Consortium) database. Data were recorded during coronary angiography among 29 studies, using 21 different cuff BP devices. ISH was defined as ≥130/<80 mm Hg using cuff BP compared with invasive aortic BP as the reference. The prevalence of ISH was 24% (n=407) according to cuff BP but 38% (n=642) according to invasive aortic BP. There was fair agreement (Cohen κ, 0.36) and 72% concordance between cuff and invasive aortic BP for identifying ISH. Among the 28% of subjects (n=471) with misclassification of ISH status by cuff BP, 20% (n=96) of the difference was due to lower cuff systolic BP compared with invasive aortic systolic BP (mean, -16.4 mm Hg [95% CI, -18.7 to -14.1]), whereas 49% (n=231) was from higher cuff diastolic BP compared with invasive aortic diastolic BP (+14.2 mm Hg [95% CI, 11.5-16.9]). In conclusion, compared with invasive BP, cuff BP fails to identify ISH in a sizeable portion of older people and demonstrates the need to improve cuff BP measurements.
CRIS-Team Scopus Importer:2021-02-05
Keywords: aorta; blood pressure; coronary angiography; hypertension; prevalence

IMPACT OF BLOOD PRESSURE AND AGEING ON RETINAL NEURODEGENERATION ASSESSED BY SPECTRAL-DOMAIN OPTICAL COHERENCE TOMOGRAPHY - Jung, Susan; Bosch, Agnes; Kohler, N.; Ott, Christian; Kannenkeril, Dennis; Dienemann, T.; Harazny, J. M.; Michelson, Georg; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

Impact of renal denervation on tissue Na(+) content in treatment-resistant hypertension - Ott, Christian; Kopp, Christoph; Dahlmann, Anke; Schmid, Andrea; Linz, Peter; Hammon, Matthias; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Titze, Jens; Schmieder, Roland; Cavallaro, Alexander Josef (Clinical Research in Cardiology, 2017)
Renal denervation (RDN) has been introduced for reducing blood pressure (BP) in treatment-resistant hypertension (TRH). The precise mechanism how RDN exerts its BP-lowering effects are not yet fully understood. It is widely accepted that sodium (Na(+)) plays a crucial role in the pathogenesis of hypertensive disease. However, there is increasing evidence of osmotically inactive Na(+) storage. We investigated the impact of RDN on Na(+) homeostasis using estimation of salt intake, and measurement of tissue Na(+) content.In a study 41 patients with TRH (office BP >=140/90 mmHg and diagnosis confirmed by 24-h ambulatory BP monitoring) underwent RDN. Tissue Na(+) content was assessed non-invasively with 3.0 T magnetic resonance imaging before and 6 months after RDN. In addition, 24-h urinary Na(+) excretion as an estimate of salt intake and spot urine Na(+)/K(+) excretion were assessed. The study was registered at http://www.clinicaltrials.gov (ID: NCT01687725).There was a significant fall in BP (office: -17 ± 20/-10 ± 12 mmHg; 24-h: -11 ± 13/-6 ± 9 mmHg, all p < 0.001) 6 months after RDN. In contrast, tissue Na(+) content of the muscle (20.1 ± 3.9 vs. 20.7 ± 4.0 mmol/L, p = 0.229) and skin (24.4 ± 6.5 vs. 24.8 ± 6.6 mmol/L, p = 0.695) did not change after RDN. Moreover, there was also no change in salt intake after RDN, whereas Na(+)/K(+) ratio only acutely increased.Although RDN resulted in a substantial reduction of BP, tissue Na(+) content of the muscle and skin was not mobilized and reduced. These data indicate that the BP reduction after RDN is unrelated to Na(+) homeostasis.
EVALuna2:3743

Impaired excitability of renal afferent innervation after exposure to the inflammatory chemokine CXCL1 - Ditting, Tilmann; Freisinger, Wolfgang; Rodionova, Kristina; Schatz, Johannes; Lale, Nena; Heinlein, Sonja; Linz, Peter; Ott, Christian; Schmieder, Roland; Scrogin, Karie E.; Veelken, Roland (American Journal of Physiology-Renal Physiology, 2016)
Recently, we showed that renal afferent neurons exhibit a unique firing pattern, i.e., predominantly sustained firing, upon stimulation. Pathological conditions such as renal inflammation likely alter excitability of renal afferent neurons. Here, we tested whether the proinflammatory chemokine CXCL1 alters the firing pattern of renal afferent neurons. Rat dorsal root ganglion neurons (Th11-L2), retrogradely labeled with dicarbocyanine dye, were incubated with CXCL1 (20 h) or vehicle before patch-clamp recording. The firing pattern of neurons was characterized as tonic, i.e., sustained action potential (AP) firing, or phasic, i.e., <5 APs following current injection. Of the labeled renal afferents treated with vehicle, 58.9% exhibited a tonic firing pattern vs. 7.8%, in unlabeled, nonrenal neurons (P < 0.05). However, after exposure to CXCL1, significantly more phasic neurons were found among labeled renal neurons; hence the occurrence of tonic neurons with sustained firing upon electrical stimulation decreased (35.6 vs. 58.9%, P < 0.05). The firing frequency among tonic neurons was not statistically different between control and CXCL1-treated neurons. However, the lower firing frequency of phasic neurons was even further decreased with CXCL1 exposure [control: 1 AP/600 ms (1-2) vs. CXCL1: 1 AP/600 ms (1-1); P < 0.05; median (25th-75th percentile)]. Hence, CXCL1 shifted the firing pattern of renal afferents from a predominantly tonic to a more phasic firing pattern, suggesting that CXCL1 reduced the sensitivity of renal afferent units upon stimulation.
EVALuna2:3740

Impaired increase of retinal capillary blood flow to flicker light exposure in arterial hypertension - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Bauernschubert, Philipp; Lehmann, Marina; Michelson, Georg; Schmieder, Roland (Hypertension, 2012)
We hypothesized that the increase of retinal capillary blood flow (RCF) to flicker light exposure is impaired in subjects with arterial hypertension. In 146 nondiabetic untreated male subjects with (n=50) or without (n=96) arterial hypertension, RCF was measured before and after flicker light exposure noninvasively and in vivo using scanning laser Doppler flowmetry. In addition, in a subgroup of 28 subjects, the change of RCF to flicker light exposure was again assessed during parallel infusion of nitric oxide synthase inhibitor N-monomethyl-l-arginine (L-NMMA). The increase of RCF to flicker light exposure was lower in patients with untreated hypertension compared with normotensive subjects when expressed in absolute terms (7.69±54 versus 27.2±44 AU; P adjusted=0.013) or percent changes (2.95±14 versus 8.33±12%; P adjusted=0.023). Systolic (?=-0.216; P=0.023) but not diastolic blood pressure (?=-0.117; P=0.243) or mean arterial pressure (?=-0.178; P=0.073) was negatively related to the percent change of RCF to flicker light exposure, independently of other cardiovascular risk factors. In the subgroup of 28 subjects, the increase of RCF to flicker light exposure was similar at baseline and during parallel infusion of L-NMMA when expressed in absolute terms (20.0±51 versus 22.6±56 AU; P=0.731) or percent changes (7.12±16 versus 8.29±18%; P=0.607). The increase of RCF to flicker light exposure is impaired in arterial hypertension. In the subgroup of the total study cohort, nitric oxide was not a major determinant of the increase of RCF to flicker light exposure.
EVALuna2:3575

Improvement in Retinal Capillary Rarefaction After Valsartan Treatment in Hypertensive Patients - Jumar, Agnes; Harazny, Joanna M.; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Schmieder, Roland (Journal of Clinical Hypertension, 2016)
Decreased capillary density influences vascular resistance and perfusion. The authors aimed to investigate the influence of the renin-angiotensin receptor blocker valsartan on retinal capillary rarefaction in hypertensive patients. Retinal vascular parameters were measured noninvasively and in vivo by scanning laser Doppler flowmetry before and after 4 weeks of treatment with valsartan in 95 patients with hypertension stage 1 or 2 and compared with 55 healthy individuals. Retinal capillary rarefaction was determined with the parameters intercapillary distance (ICD) and capillary area (CapA). In hypertensive patients, ICD decreased (23.4±5.5 ?m vs 21.5±5.6 ?m, P<.001) and CapA increased (1564±621 vs 1776±795, P=.001) after valsartan treatment compared with baseline. Compared with healthy normotensive controls (ICD 20.2±4.2 ?m, CapA 1821±652), untreated hypertensive patients showed greater ICD (P<.001) and smaller CapA (P=.019), whereas treated hypertensive patients showed no difference in ICD (P=.126) and CapA (P=.728). Therapy with valsartan for 4 weeks diminished capillary rarefaction in hypertensive patients.
EVALuna2:3866

Improvement of albuminuria after renal denervation - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Ewen, Sebastian; Ukena, Christian; Uder, Michael; Boehm, Michael; Schmieder, Roland (International Journal of Cardiology, 2014)
The primary objective of this study was the effect of renal denervation (RDN) on elevated urinary albumin-to-creatinine ratio (UACR) in treatment-resistant hypertensive patients. In addition, patients were stratified according their UACR at baseline into micro- (30-300 mg/g, n=37) and macroalbuminuria (>= 300 mg/g, <2,200 mg/g, n=22).Increased albuminuria indicates cardiovascular and renal damage in hypertension. RDN emerged as an innovative interventional approach to reduce blood pressure (BP) and may thus reduce albumin urinary excretion.Fifty-nine treatment-resistant hypertensive patients with elevated UACR at baseline underwent catheter-based RDN using the Symplicity Flex(TM) catheter (Medtronic Inc., Santa Rosa, CA).In the whole and pre-specified subgroups both office and 24-h ambulatory BP were significantly reduced 6 months after RDN. In parallel, a significant reduction in UACR occurred in all patients (160 (65-496) versus 89 (29-319) mg/g creatinine, p<0.001) and in both subgroups (microalbuminuria: 83 (49-153) versus 58 (17-113) mg/g creatinine, p=0.001; macroalbuminuria: (536 (434-1483) versus 478 (109-1080) mg/g creatinine, p<0.001). In accordance, the prevalence of micro- and macroalbuminuria decreased significantly. Regression analysis revealed a modest positive relationship between the decrease of UACR and the fall of systolic BP (?=0.340, p=0.039) independent of renal function. Renal function remained unchanged after RDN.In summary, following RDN, the magnitude of albuminuria as well as the prevalence of micro- and macroalbuminuria decreased in treatment-resistant hypertensive patients. Since albuminuria is an independent renal and cardiovascular risk factor, our findings suggest a reduction of renal and cardiovascular risk in these patients.
EVALuna2:3681

Influence of Age on Upper Arm Cuff Blood Pressure Measurement - Picone, Dean S.; Schultz, Martin G.; Otahal, Petr; Black, J. Andrew; Bos, Willem J.; Chen, Chen Huan; Cheng, Hao Min; Cremer, Antoine; Dwyer, Nathan; Fonseca, Ricardo; Hughes, Alun D.; Kim, Hack Lyoung; et al. (Hypertension, 2020)
Blood pressure (BP) is a leading global risk factor. Increasing age is related to changes in cardiovascular physiology that could influence cuff BP measurement, but this has never been examined systematically and was the aim of this study. Cuff BP was compared with invasive aortic BP across decades of age (from 40 to 89 years) using individual-level data from 31 studies (1674 patients undergoing coronary angiography) and 22 different cuff BP devices (19 oscillometric, 1 automated auscultation, 2 mercury sphygmomanometry) from the Invasive Blood Pressure Consortium. Subjects were aged 64±11 years, and 32% female. Cuff systolic BP overestimated invasive aortic systolic BP in those aged 40 to 49 years, but with each older decade of age, there was a progressive shift toward increasing underestimation of aortic systolic BP (P<0.0001). Conversely, cuff diastolic BP overestimated invasive aortic diastolic BP, and this progressively increased with increasing age (P<0.0001). Thus, there was a progressive increase in cuff pulse pressure underestimation of invasive aortic PP with increasing decades of age (P<0.0001). These age-related trends were observed across all categories of BP control. We conclude that cuff BP as an estimate of aortic BP was substantially influenced by increasing age, thus potentially exposing older people to greater chance for misdiagnosis of the true risk related to BP.
CRIS-Team Scopus Importer:2020-03-17
Keywords: aging; cardiovascular disease; coronary angiography; risk factor; sphygmomanometers

Influence of blood flow on arteriolar wall-to-lumen ratio in the human retinal circulation in vivo - Ritt, Martin; Harazny, Joanna M.; Ott, Christian; Raff, Ulrike; Lehmann, Marina; Michelson, Georg; Schmieder, Roland (Microvascular Research, 2012)
We hypothesized that blood flow impacts on arteriolar wall-to-lumen ratio and that vasodilatory capacity is negatively related to arteriolar wall-to-lumen ratio in the human retinal vascular bed.The study cohort comprised 141 non-diabetic untreated male patients with (n=52) or without (n=89) arterial hypertension but without evidence for cardiovascular disease. Retinal capillary blood flow (RCF) before and after exposure to flicker light and to infusion of nitric oxide (NO) synthase inhibitor N-monomethyl-l-arginine (L-NMMA), and parameters of retinal arteriolar morphology, e.g. wall-to-lumen ratio, were assessed non-invasively and in vivo by scanning laser Doppler flowmetry.The study cohort was grouped according to the median RCF into two groups. Patients with RCF above the median revealed lower wall-to-lumen ratio (0.30±0.1 vs 0.34±0.1 (-), P adjusted=0.023) compared to patients with RCF equal or below the median. In addition, RCF was negatively related to wall-to-lumen ratio independently of cardiovascular risk factors (ß=-0.224, P=0.026). In parallel, the decrease of RCF to L-NMMA infusion was greater in patients with RCF above the median compared to the counter group (-8.95±11 vs. 0.35±15 (%), P adjusted <0.001). The increase in RCF to flicker light exposure was negatively related to wall-to-lumen ratio in hypertensive but not in normotensive or all patients (r=-0.292, P=0.047, r=-0.035, P=0.746 and r=-0.126, P=0.144, respectively).In the retinal circulation blood flow impacts on arteriolar wall-to-lumen ratio. Basal NO activity might modulate blood flow and arteriolar morphological changes. In hypertensive, but not in normotensive patients, the vasodilatory capacity is negatively related to arteriolar wall-to-lumen ratio in the human retinal vascular bed.
EVALuna2:3527

Interdisciplinary German clinical practice guidelines on the management of type B aortic dissection Interdisziplinäre deutsche Leitlinien für die klinische Praxis zur Behandlung der Aortendissektion Typ B - Oberhuber, A.; Raddatz, A.; Betge, S.; Ploenes, C.; Ito, W.; Janosi, R. A.; Ott, Christian; Langheim, E.; Czerny, M.; Puls, R.; Maßmann, A.; Zeyer, K.; et al. (Gefässchirurgie, 2023)
CRIS-Team Scopus Importer:2023-05-05

INTRARENAL HIGH SALT ADMINISTRATION CAUSES TONIC INHIBITION OF RENAL SYMPATHETIC NERVE ACTIVITY (RSNA) - Hindermann, Martin; Rodionova, Kristina; Dietz, Amelie; Ditting, Tilmann; Ott, Christian; Schmieder, Roland; Amann, Kerstin Ute; Veelken, Roland (2018)
EVALuna2:204842

Invasive treatment of resistant hypertension: present and future - Ott, Christian; Schmieder, Roland (Current Hypertension Reports, 2014)
The underlying pathophysiologic concept of diverse invasive devices to treat resistant hypertension (e.g., sympathetic denervation, carotid sinus nerve stimulation) is known for a long time. Since the pioneering work in the 1940s in humans, innovative techniques have been developed resulting in less invasive treatment procedures and, hence, overcoming serious side effects, which in turn improved safety and lead to more widespread use. Recently, new experimental technologies have been or are under evaluation in experiments and first-in-man studies have been conducted. Data with interventional techniques are rapidly expanding and have to be interpreted with caution. Additional data from randomized potentially sham-controlled studies are urgently needed. This article focuses on the increasing work of different invasive approaches for the treatment of resistant hypertension.
EVALuna2:3692

IS BASAL NITRIC OXIDE ACTIVITY OF THE RENAL VASCULATURE ALTERED? ANALYSIS OF A RANDOMIZED CONTROLLED TRIAL COMPARING TWO COMBINATION THERAPIES - Kannenkeril, Dennis; Ott, Christian; Bosch, Agnes; Striepe, Kristina; Pietschner, Robert; Schiffer, Mario; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2022)
CRIS-Team WoS Importer:2023-02-17

IS BASAL NITRIC OXIDE ACTIVITY OF THE RENAL VASCULATURE ALTERED? ANALYSIS OF A RANDOMIZED CONTROLLED TRIAL COMPARING TWO COMBINATION THERAPIES - Kannenkeril, Dennis; Ott, Christian; Bosch, Agnes; Striepe, Kristina; Pietschner, Robert; Schiffer, Mario; Schmieder, Roland (Journal of Hypertension, 2022)
OBJECTIVE: Recently we demonstrated that a combination therapy with empagliflozin and linagliptin in patients with type 2 diabetes mellitus (T2DM) induce changes in renal hemodynamics. The purpose of this study was to analyze the influence of basal nitric oxide (NO) activity of the renal vasculature on the described changes of the renal hemodynamic profile. DESIGN AND METHOD: In this study patients with T2DM were nalysing to receive either empagliflozin and linagliptin (E+L group, n = 50) or metformin and insulin glargine (M+I group, n = 46), for 3 months. Renal hemodynamics were assessed with constant-infusion input-clearance technique with p-aminohippuric acid for renal plasma flow (RPF) and inulin for glomerular filtration rate (GFR) at baseline and after treatment. Due to withdrawal of inulin from the market during the study, GFR and filtration fraction (FF) were measured only in a sub-group of patients (E+L: n = 34; M+I: n = 31). Intraglomerular hemodynamics were calculated according the model established by Gomez. The basal NO activity in the renal circulation has been assessed by nalysing change in RPF in response to intravenously administrated NG-monomethyl-l-arginine (NO inhibitor). RESULTS: After 3 months of treatment, we did not observe any change in basal NO activity compared to baseline in either of the groups. In the E+L group, we found a correlation between basal NO activity of the renal vasculature after 3 months of treatment and change in RPF (r = -0.535, p < 0.001), renal blood flow (r = -0.468, p = 0.001) and renal vascular resistance (r = 0.377, p = 0.007) induced by treatment. Similar correlations with change in FF (r = 0.639, p < 0.001), preglomerular (r = 0.350, p = 0.046) and postglomerular resistance (r = 0.588, p < 0.001) have been found. No such relationships were found in the M+I group after 3 months and with basal NO activity at baseline in both treatment groups. CONCLUSIONS: Basal NO emerged as a determinant of the renal hemodynamic response in the combination therapy of empagliflozin and linagliptin, but not in the combination therapy of insulin and metformin.
CRIS-Team Scopus Importer:2022-09-09

LOW DOSE-EPLERENONE TREATMENT DECREASES AORTIC STIFFNESS IN PATIENTS WITH METABOLIC SYNDROME - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Schiffer, Mario; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Mid-Term Vascular Safety of Renal Denervation Assessed by Follow-up MR Imaging. - Schmid, Axel; Schmieder, Raphael; Lell, Michael; Janka, Rolf Matthias; Veelken, Roland; Schmieder, Roland; Uder, Michael; Ott, Christian (Cardiovascular and Interventional Radiology, 2016)
Renal denervation (RDN) emerged as a treatment option for reducing blood pressure (BP) in patients with treatment-resistant hypertension (TRH). However, concerns have been raised regarding the incidence of late renal artery stenosis or thromboembolism after RDN. The goal of the current study was, therefore, to conduct a prospective clinical trial on the mid-term vascular integrity of the renal arteries and the perfusion of the renal parenchyma assessed by magnetic resonance imaging (MRI) in the follow-up after catheter-based RDN.In our single-centre investigator initiated study, 51 patients with true TRH underwent catheter-based RDN using the Symplicity Flex(TM) catheter (Medtronic Inc., Palo Alto, CA). Follow-up MRI was performed at a median of 11 months (interquartile range 6-18 months) after RDN on a 1.5T MR unit. High-resolution MR angiography (MRA) and MRI results were compared to the baseline digital angiography of renal arteries obtained at time of RDN. In case of uncertainties (N = 2) catheter angiography was repeated.Both office and 24-h ambulatory BP were significantly reduced 6 and 12 months after RDN. Renal function remained unchanged 6 and 12 months after RDN. In all patients, MRA excluded new or progression of pre-existing low grade renal artery stenosis as well as focal aneurysms at the sites of radiofrequency ablation. In none of the patients new segmental perfusion deficits in either kidney were detected on MRI.No vascular or parenchymal complications after radiofrequency-based RDN were detected in 51 patients followed up by MRI.
EVALuna2:3794

Myocardial infarction with a preserved ejection fraction—the impaired function of the cardio-renal baroreflex - Pickny, Lisa; Hindermann, Martin; Ditting, Tilmann; Hilgers, Karl Friedrich; Linz, Peter; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Rodionova, Kristina (Frontiers in Physiology, 2023)
Introduction: In experimental myocardial infarction with reduced ejection fraction causing overt congestive heart failure, the control of renal sympathetic nerve activity (RSNA) by the cardio-renal baroreflex was impaired. The afferent vagal nerve activity under these experimental conditions had a lower frequency at saturation than that in controls. Hence, by investigating respective first neurons in the nodose ganglion (NG), we wanted to test the hypothesis that after myocardial infarction with still-preserved ejection fraction, the cardiac afferent nerve pathway is also already impaired. Material and methods: A myocardial infarction was induced by coronary artery ligature. After 21 days, nodose ganglion neurons with cardiac afferents from rats with myocardial infarction were cultured. A current clamp was used to characterize neurons as “tonic,” i.e., sustained action potential (AP) firing, or “phasic,” i.e., <5 APs upon current injection. Cardiac ejection fraction was measured using echocardiography; RSNA was recorded to evaluate the sensitivity of the cardiopulmonary baroreflex. Renal and cardiac histology was studied for inflammation and fibrosis markers. Results: A total of 192 neurons were investigated. In rats, after myocardial infarction, the number of neurons with a tonic response pattern increased compared to that in the controls (infarction vs. control: 78.6% vs. 48.5%; z-test, *p < 0.05), with augmented production of APs (23.7 ± 2.86 vs. 15.5 ± 1.86 APs/600 ms; mean ± SEM, t-test, *p < 0.05). The baseline activity of RSNA was subtly increased, and its control by the cardiopulmonary baroreflex was impaired following myocardial infarction: the fibrosis marker collagen I augmented in the renal interstitium. Discussion: After myocardial infarction with still-preserved ejection fraction, a complex impairment of the afferent limb of the cardio-renal baroreflex caused dysregulation of renal sympathetic nerve activity with signs of renal fibrosis.
CRIS-Team Scopus Importer:2023-05-05
Keywords: cardiac afferent neurons after myocardial infarction cardiac afferent innervation; congestive heart failure; myocardial infarction; neuronal cell culture; preserved ejection fraction; renal innervation

Negative Impact of the UEFA European Soccer Championship on Central Hemodynamics and Arterial Stiffness: A Multicenter Study - Franzen, Klaas F.; Mortensen, Kai; Ott, Christian; Herber, Katrin; Busse, Marlene; Soling, Charlotte; Schneppe, Daniel; Lassig, Saskia; Dorr, Marcus; Tilz, Roland; Dromann, Daniel; Schunkert, Heribert; et al. (Life, 2022)
(1) Background: watching sporting events may trigger cardiovascular events by elevating emotional stress levels. The underlying reasons and specific populations at risk are not well defined. (2) Methods: we conducted a multicenter prospective trial at three German sites during the UEFA Soccer EC 2012 and 2021 comprising 52 healthy participants (noCVD) and 18 patients hospitalized with cardiovascular disease (CVD). Subjects were studied during matches of the German national team (GP) as well as corresponding matches without German participation (noGP). Peripheral and central blood pressure (BP) and parameters of arterial stiffness were measured (Mobil-O-Graph™, I.E.M., Stolberg, Germany) before, during, and after the matches. (3) Results: in terms of CVD, peripheral as well as central BP and heart rate increased significantly during GP as well as noGP matches and remained elevated beyond the end of the matches. Likewise, arterial stiffness parameters and vascular resistance were higher during the matches and remained elevated after the matches. No consistent significant differences were found between GP and noGP matches. (4) Conclusions: this is the first study on real-life changes in hemodynamics during sport-associated emotional stress, with comparison between noCVD and CVD. We found that alterations were profound in CVD and remained elevated even after the matches.
CRIS-Team Scopus Importer:2022-11-25
Keywords: arterial stiffness; cardiovascular disease; central hemodynamics; emotional stress; European soccer championship

Neurogenic substance P-influences on action potential production in afferent neurons of the kidney? - Rodionova, Kristina; Hilgers, Karl Friedrich; Linz, Peter; Schaetzl, Johannes; Raschke, Giulia; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2021)
We recently showed that a substance P (SP)-dependent sympatho-inhibitory mechanism via afferent renal nerves is impaired in mesangioproliferative nephritis. Therefore, we tested the hypothesis that SP released from renal afferents inhibits the action potential (AP) production in their dorsal root ganglion (DRG) neurons. Cultured DRG neurons (Th11-L2) were investigated in current clamp mode to assess AP generation during both TRPV1 stimulation by protons (pH 6) and current injections with and without exposure to SP (0.5 mu mol) or CGRP (0.5 mu mol). Neurons were classified as tonic (sustained AP generation) or phasic (<= 4 APs) upon current injection; voltage clamp experiments were performed for the investigation of TRPV1-mediated inward currents due to proton stimulation. Superfusion of renal neurons with protons and SP increased the number of action potentials in tonic neurons (9.6 +/- 5 APs/10 s vs. 16.9 +/- 6.1 APs/10 s, P < 0.05, mean +/- SD, n = 7), while current injections with SP decreased it (15.2 +/- 6 APs/600 ms vs. 10.2 +/- 8 APs/600 ms, P < 0.05, mean +/- SD, n = 29). Addition of SP significantly reduced acid-induced TRPV1-mediated currents in renal tonic neurons (- 518 +/- 743 pA due to pH 6 superfusion vs. - 82 +/- 50 pA due to pH 6 with SP superfusion). In conclusion, SP increased action potential production via a TRPV1-dependent mechanism in acid-sensitive renal neurons. On the other hand, current injection in the presence of SP led to decreased action potential production. Thus, the peptide SP modulates signaling pathways in renal neurons in an unexpected manner leading to both stimulation and inhibition of renal neuronal activity in different (e.g., acidic) environmental contexts.
CRIS-Team WoS Importer:2021-04-16

Neurogenic tachykinin mechanisms in experimental nephritis of rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Paulus, Eva-Maria; Tiegs, Gisa; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; Ditting, Tilmann (Pflügers Archiv: European Journal of Physiology, 2020)
We demonstrated earlier that renal afferent pathways combine very likely "classical" neural signal transduction to the central nervous system and a substance P (SP)-dependent mechanism to control sympathetic activity. SP content of afferent sensory neurons is known to mediate neurogenic inflammation upon release. We tested the hypothesis that alterations in SP-dependent mechanisms of renal innervation contribute to experimental nephritis. Nephritis was induced by OX-7 antibodies in rats, 6 days later instrumented for recording of blood pressure (BP), heart rate (HR), drug administration, and intrarenal administration (IRA) of the TRPV1 agonist capsaicin to stimulate afferent renal nerve pathways containing SP and electrodes for renal sympathetic nerve activity (RSNA). The presence of the SP receptor NK-1 on renal immune cells was assessed by FACS. IRA capsaicin decreased RSNA from 62.4 +/- 5.1 to 21.6 +/- 1.5 mV s (*p < 0.05) in controls, a response impaired in nephritis. Suppressed RSNA transiently but completely recovered after systemic administration of a neurokinin 1 (NK1-R) blocker. NK-1 receptors occurred mainly on CD11(+)dendritic cells (DCs). An enhanced frequency of CD11c(+)NK1R(+)cell, NK-1 receptor(+)macrophages, and DCs was assessed in nephritis. Administration of the NK-1R antagonist aprepitant during nephritis reduced CD11c(+)NK1R(+)cells, macrophage infiltration, renal expression of chemokines, and markers of sclerosis. Hence, SP promoted renal inflammation by weakening sympathoinhibitory mechanisms, while at the same time, substance SP released intrarenally from afferent nerve fibers aggravated immunological processes i.e. by the recruitment of DCs.
CRIS-Team WoS Importer:2020-11-06

New software analyses increase the reliability of measurements of retinal arterioles morphology by scanning laser Doppler flowmetry in humans - Harazny, Joanna M.; Raff, Ulrike; Welzenbach, Juergen; Ott, Christian; Ritt, Martin; Lehmann, Maria; Michelson, Georg; Schmieder, Roland; Lehmann, Maria (Journal of Hypertension, 2011)
The investigation of the retinal arterioles offers the unique opportunity to analyze in vivo arteriolar remodeling in arterial hypertension in humans. We analyzed the reliability of assessing retinal arteriolar morphology with our new version of the software analyses for scanning laser Doppler flowmetry.In the test-retest reliability study, 10 eyes of 10 healthy persons were measured during 5 days under routine laboratory conditions with the Heidelberg Retinal Flowmetry. In a second study, interobserver and intraobserver reliability was analyzed from retinal images of 18 patients with three types of arterial hypertension by three readers and the most experienced reader analyzed all images twice on two different days. Images were analyzed by the old and the newly developed software versions. To characterize the reliability, the coefficients of variation were calculated.The test-retest study analyzed with the new program showed that the variation coefficients of vessel and lumen diameter, wall thickness, wall/lumen ratio and new calculated parameter: lumen/vessel diameter ratio of retinal arterioles were significantly less than 10%, with the exception of the wall cross-sectional area (12.5%). The interobserver and intraobserver reliability showed in nearly all circumstances coefficients of variations of less than 10% and did not differ across various readers and patient groups.The new software 'SLDF version 4.0' clearly improved the reliability of assessing the structural parameters of the retinal arterioles. The application delivers reliable measurements of the retinal arteriolar structure in vivo in human
EVALuna2:3487

Non-invasive Renal Denervation: Update on External Ultrasound Approaches - Schmieder, Roland; Ott, Christian; Bramlage, Peter (Current Hypertension Reports, 2016)
In the last decade, intravenous renal denervation (RDN) has emerged as an alternative to pharmacological treatment in patients with resistant hypertension, but currently involves an invasive and technically challenging procedure. The Surround Sound(TM) system utilises externally delivered ultrasound to achieve RDN using a completely non-invasive, automated real-time tracking system coupled with a therapeutic delivery module thereby addressing these limitations. A brief history, technical overview and summary of preclinical and clinical studies of the KonaMedical Surround Sound(TM) system are presented. A literature search using the terms "renal denervation", "resistant hypertension" and "external ultrasound" was performed using PubMed, and references retrieved were selected based on relevancy and year of publication (date range 1991-2015). The Surround Sound(TM) system appears to be a promising approach to RDN which eliminates several of the factors currently limiting the intravenous approach. So far, it has demonstrated efficacy for reducing blood pressure in resistant hypertension patients with minimal adverse effects. Several double-blind, sham-controlled clinical trials are currently underway to confirm the validity of these findings.
EVALuna2:3851

Olmesartan improves pulse wave velocity and lowers central systolic blood pressure and ambulatory blood pressure in patients with metabolic syndrome - Raff, Ulrike; Walker, Stefanie Elke; Ott, Christian; Schneider, Markus P.; Schmieder, Roland (Journal of Clinical Hypertension, 2015)
Ambulatory blood pressure (BP) and central systolic BP (cSBP) are superior to brachial office BP measurements in predicting cardiovascular end organ damage. The authors aimed to analyze the effect of olmesartan 80 mg (OLM 80) vs 20 mg (OLM 20) vs amlodipine 5 mg (AML 5) on central hemodymamics and ambulatory BP in patients with metabolic syndrome (MetS).In a double-blind, three-phase crossover study comprising 69 untreated patients with MetS defined by the Third Report of the Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults guidelines, the effects of OLM 80 on central hemodynamics (cSBP), central pulse pressure), pulse wave velocity (PWV), and 24-hour ambulatory BP were compared with OLM 20 and AML 5, given for 6 weeks each. In 69 patients (47 men, 22 women) (51.5±9.75 years), reduction in cSBP was the highest with OLM 80 and significantly greater than the reduction with AML 5 (-14.1 mm Hg vs -9.7 mm Hg, P=.0117). All three substances significantly reduced 24-hour ambulatory systolic (OLM 80 and OLM 20 P<.0001; AML 5 P=.0105). BP and 24-hour diastolic BP (OLM 80 and OLM 20 P<.0001; AML 5 P=.0126). PWV was significantly reduced by OLM 80 (-0.58 m/s, P=.0088) and by OLM 20 (-0.48 m/s, P=.0362) but not by AML 5 (-0.28 m/s, P=.2065). For PWV, no significant differences were detected between the three groups. OLM significantly improves arterial stiffness as demonstrated by the reduction in PWV and in cSBP. In addition, 24-hour ambulatory BP was reduced to a greater extent with OLM 80 than with AML 5.
EVALuna2:3748

OS 12-03 SGLT-2-INHIBITION WITH DAPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT - Schmieder, Roland; Ott, Christian; Linz, Peter; Jumar, Agnes; Friedrich, Stefanie; Titze, Jens; Hammon, Matthias; Uder, Michael; Kistner, Iris (Journal of Hypertension, 2016)
Sodium tissue content by Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and, in parallel, of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes leads to decreased tissue sodium content due to its pharmacological action.In a prospective, double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to dapagliflozin 10 mg o.d. and placebo for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analyzed the sodium content in the skin and muscles of the lower leg by the Na-MRI at baseline, after the first and second treatment phase of 6 weeks.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11, p = 0.010) and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024) 24-hour ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline (24.1 ± 6.6 vs.22.7 ± 6.4 mmol/L; p = 0.013). No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 mmol/L, p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in sodium tissue content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes known to be salt sensitive and prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition.
EVALuna2:14604

OS 28-03 SECRETORY CAPACITY OF PANCREATIC BETA CELLS IS ENHANCED 6 MONTHS AFTER RENAL DENERVATION IN TREATMENT RESISTANT HYPERTENSIVE PATIENTS - Ott, Christian; Kistner, Iris; Schmid, Axel; Friedrich, Stefanie; Ditting, Tilmann; Veelken, Roland; Mahfoud, Felix; Boehm, Michael; Uder, Michael; Schmieder, Roland (Journal of Hypertension, 2016)
Renal denervation (RDN) lowers blood pressure (BP) by interruption of sympathetic nerve activity. A high sympathetic tone increases not only BP but also decreases pancreatic beta cell insulin secretion. Hence, the objective of the study was to analyze whether RDN improves secretory capacity of beta cells.In 40 patients (7 diabetics, 19 prediabetics, 14 non diabetics) with treatment resistant hypertension (defined by office BP >= 140/90 mmHg and diagnosis confirmed with 24-h ambulatory BP >= 130/80 mmHg), insulin secretion was measured before and 6 months after RDN (Simplicity flex catheter, Medtronic) by glucagon test. At each time point blood was sampled prior to glucagon administration and 6 minutes after intravenous injection of 1 ml glucagon for measurement of C-peptide, insulin and proinsulin (by ELISA).In these 40 patients (mean age 58 ± 12 years, mean office BP 154 ± 22 mmHg / 89 ± 14 mmHg while on 5.2 ± 1.4 antihypertensive drugs) office systolic and diastolic BP was significantly reduced 6 months after RDN (both p < 0.01). Fasting plasma glucose and HbA1c level was significantly reduced 6 month after RDN (both p < 0.01). Six months after RDN, the increase of C-peptide concentration and insulin concentration after glucagon injection was significantly higher compared to before RDN (both p < 0.05).Thus, our data indicate an improved pancreatic beta cell function after RDN in patients with treatment resistant hypertension.
EVALuna2:14605

Patient preference for therapies in hypertension: a cross-sectional survey of German patients - Schmieder, Roland; Högerl, Karin; Jung, Susan; Bramlage, Peter; Veelken, Roland; Ott, Christian (Clinical Research in Cardiology, 2019)
BACKGROUND: Hypertension is poorly controlled in numerous patients despite effective medication being available. Catheter-based renal denervation (RDN) has emerged as an alternative treatment option. We aimed to assess how likely patients with elevated blood pressure (BP) are to accept RDN as treatment option. METHODS: A questionnaire-based cross-sectional survey was performed in patients with elevated BP in Germany. Data on patient demographics, clinical characteristics and treatment preferences were collected, anonymized and analyzed. RESULTS: One thousand and eleven patients completed the survey. Mean age was 66 years (55% male). If not already on medication (n = 172), 38.2% of patients would prefer RDN. Of those already on drug therapy (n = 839), 28.2% would opt for RDN. Patients who were pro-RDN were younger (p < 0.0001) and more often male (p < 0.0001). Nineteen percent would choose RDN if it lowered systolic BP by at least 20 mmHg, more than 40% if they did not have to take any more pills thereafter, and 30% if it would lower BP by at least 10 mmHg. Experiences of side effects and drug adherence were identified as determinants of patient preference. Physicians were the main source of information regarding medical problems (95.5%) and influence patients' decision regarding therapies (98%). CONCLUSIONS: This survey found that a significant proportion of patients would choose catheter-based RDN over lifelong pharmacotherapy. These patients were younger and more likely to be male but their expectation of the extent of BP decrease with RDN was high. Physicians are key mediators for treatment selection. They need to incorporate patient preferences into shared decision making.
EVALuna2:118640

PCSK-9-inhibitor therapy improves endothelial function in high-risk patients with cardiovascular disease - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Pietschner, Robert; Ott, Christian; Schiffer, Mario; Achenbach, Susanne; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

PCSK-9-inhibitor therapy improves endothelial function in high-risk patients with cardiovascular disease - Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Berner, Laura; Pietschner, Robert; Ott, Christian; Schiffer, Mario; Achenbach, Stephan; Schmieder, Roland (Clinical Research in Cardiology, 2024)
Background: Impaired endothelial function predicts cardiovascular events. The aim of this study was to analyze the effect of evolocumab on endothelial function in patients with cardiovascular disease. Methods: This was a prospective, double-blinded, randomized, controlled, single center study including patients with cardiovascular disease and treated with statins. Patients were consecutively randomized (1:1) to either evolocumab treatment or placebo. All patients underwent examination of endothelial function at baseline, and after 1, 4 and 8 weeks of treatment by a semi-automatic high-resolution ultrasound system (UNEX EF 18G). Parameters of endothelial function were flow-mediated vasodilation (FMD), low flow-mediated vasoconstriction (L-FMC) and vasoactive range (VAR). Results: Hundred three patients with a mean age of 66.2 ± 7.7 years and a mean LDL-cholesterol of 98 ± 19.1 mg/dl completed the study. The change in VAR from baseline to week 8 was significantly different with evolocumab compared to placebo (p = 0.045). Moreover, VAR increased after 8 weeks of treatment with evolocumab compared to baseline (p = 0.034). No change has been noticed in FMD and L-FMC after 8 weeks of treatment with evolocumab. In subgroup analyses, VAR improved in patients with age ≤ 67 years, lower systolic blood pressure (≤ 125 mmHg) and higher baseline LDL-cholesterol (> 95 mg/dl), (p = 0.006, p = 0.049 and p = 0.042, respectively) after 8 weeks of evolocumab treatment. No serious adverse event related to study medication occurred during the study. Conclusion: Our data indicate that endothelial function improved with evolocumab treatment in high-risk patients on statin therapy with preexisting cardiovascular disease. Our results contribute to the mechanistic explanation why lower incidence of the cardiovascular composite endpoint has been demonstrated in the FOURIER study. Graphical abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-11-29
Keywords: Endothelial function; Evolocumab; Flow-mediated vasodilation; PCSK-9 inhibitor; Vasoactive range

Phase II randomized sham-controlled study of renal denervation for individuals with uncontrolled hypertension - WAVE IV - Schmieder, Roland; Ott, Christian; Toennes, Stefan W.; Bramlage, Peter; Gertner, Michael; Dawood, Omar; Baumgart, Peter; O'Brien, Benjamin; Dasgupta, Indranil; Nickenig, Georg; Ormiston, John; Saxena, Manish; et al. (Journal of Hypertension, 2017)
The aim of this double-blind, randomized, sham-controlled study was to verify the blood pressure (BP)-lowering efficacy of externally delivered focused ultrasound for renal denervation (RDN).Nonrandomized, first proof-of-concept study and experimental evidence suggested that noninvasive techniques of RDN emerged as an alternative approach of RDN to invasive technologies.WAVE IV, an international, randomized (1 : 1) sham-controlled, double-blind prospective clinical study, was prematurely stopped. Patients were enrolled if office BP was at least 160 mmHg and 24-h ambulatory BP was at least 135 mmHg, while taking three or more antihypertensive medications. The treatment consisted of bilateral RDN using therapeutic levels of ultrasound energy and the sham consisted of bilateral application of diagnostic levels of ultrasound energy.In the 81 treated patients neither changes in office BP at 12 and 24 weeks, nor changes in 24-h ambulatory BP at 24-week follow-up visit differed between the two groups significantly. Of note, no safety signal was observed. Adherence analysis disclosed full adherence in 77% at baseline and 82% at 6 months' follow-up visit. Post hoc analysis revealed that stricter criteria for stabilization of BP at baseline were associated with a numerically greater change in 24-h ambulatory BP in the RDN group than in the sham group.Our data did not prove that antihypertensive efficacy of the externally delivered focused ultrasound for RDN was greater than the sham effect. Stabilization of BP at baseline was identified as an important determinant of BP changes.
EVALuna2:4028

Pleiotropic effects under combined therapy with empagliflozin and linagliptin compared to metformin and insulin glargine in patients with type 2 diabetes - Jung, Susan; Ott, Christian; Kannenkeril, Dennis; Bosch, Agnes; Karg, M.; Striepe, Kristina; Bramlage, P.; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

Predictors of blood pressure response after renal denervation beyond pretreatment blood pressure - Schmieder, Roland; Delles, C.; Lauder, L.; Ott, Christian; Boehm, M.; Mahfoud, F. (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Prevention of electrocardiographic left ventricular remodeling by the angiotensin receptor blocker olmesartan in patients with type 2 diabetes - Raff, Ulrike; Ott, Christian; Ruilope, Luis M.; Menne, Jan; Haller, Hermann; Schmieder, Roland (Journal of Hypertension, 2014)
To assess the ability of olmesartan (OLM) to prevent or delay left ventricular remodeling and hypertrophy in patients with type 2 diabetes.This prespecified ECG substudy of Randomised OlmesArtan and Diabetes MicroAlbuminuria Prevention (ROADMAP), which compared OLM with placebo, assessed the signs of left ventricular remodeling in patients with a 12-lead ECG at baseline and after at least 2 years. Cornell voltage QRS duration product (primary objective), Cornell voltage index and Sokolow-Lyon index were assessed.In total, 9418 ECG recordings and 1513 patients from ROADMAP were analyzed (placebo, n = 736; OLM, n = 777). Quartiles defined by baseline Cornell voltage QRS duration product were assessed and the proportion of patients in the highest quartile (>=200 mVms) increased from 24.0 to 26.5% in the placebo group and decreased from 25.5 to 22.3% in the OLM group [odds ratio (OR) 0.598 (95% confidence interval [CI] 0.440-0.813); P = 0.0011]. The OR did not change after adjustment for baseline parameters. By the end of study, 38.7% of patients in the placebo group and 34.7% in the OLM group shifted from a lower to a higher quartile or remained in the highest quartile of Cornell voltage QRS duration product [OR 0.797 (95% CI 0.637-0.996); P = 0.0465]. This translated into a 20.3% risk reduction with OLM and suggested OLM attenuated the progression of left ventricular remodeling versus placebo.OLM substantially delayed the development of left ventricular remodeling in type 2 diabetes. This effect was not explained by the differences in blood pressure control. Thus, OLM delayed the onset of microalbuminuria, as well as the ECG signs of cardiac structural adaptation in type 2 diabetes.
EVALuna2:3738

Reduced tissue sodium content is related to improvement of vascular function in patients with chronic heart failure treated with the SGLT2 inhibitor empagliflozin - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, P.; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Reduction of tissue sodium content by SGLT-2-inhibition with dapagliflozin - Karg, M. V.; Ott, Christian; Linz, Peter; Jumar, A.; Kannenkeril, Dennis; Titze, J.; Hammon, Matthias; Uder, Michael; Schmieder, Roland (2017)
EVALuna2:36268

RELATION BETWEEN NOISE ANNOYANCE, STRESS HORMONES AND THE RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Rauh, Manfred; Ott, Christian; Striepe, Kristina; Jung, Susanne; Kolwelter, Julie; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Relation between waist circumference and the renal hemodynamic in healthy individuals - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Striepe, Kristina; Schiffer, Mario; Schmieder, Roland (Nutrition Metabolism and Cardiovascular Diseases, 2024)
Background and aims: Obesity has been shown to be an independent risk factor for the development of CKD. Little is known about pathways of interaction of visceral fat mass estimated by waist circumference (WC) and metabolic factors with the renal and intraglomerular hemodynamic profile in healthy, non-obese individuals. Methods and results: The study population of this post-hoc analysis in 80 healthy individuals, who participated in a randomized, controlled clinical trial (www.clinicaltrials.gov: NCT02783456) was divided into two groups based on median of WC (high WC and low WC group). Renal hemodynamic profiles were analyzed using steady state input clearance (infusion of para-amino-hippuric acid and inulin). Intraglomerular pressure (IGP) and resistances of the afferent (RA) and efferent (RE) arterioles were calculated (Gomez equation). The analysis included healthy, non-smoking individuals, aged 27 ± 9 years with median WC of 84.75 ± 9 cm. Glomerular filtration rate (GFR) (110 ± 15 vs. 127 ± 16 ml/min/m2, p < 0.001), renal plasma flow (RPF) (620 ± 109 vs. 700 ± 104 ml/min, p = 0.001) and IGP (36.7 ± 2.3 vs. 38.5 ± 3.1 mmHg, p = 0.003) were lower in the high WC compared to the low WC group. Patients in the high WC group showed higher renal vascular resistance (RVR) (85 ± 19 vs. 70 ± 12 mmHg/(ml/min), p < 0.001), higher RA (4034 ± 1177 vs. 3069 ± 786 dyn∗s/cm5, p < 0.001) and higher RE (2283 ± 339 vs. 2118 ± 280 dyn∗s/cm5, p = 0.021) compared to the low WC group. Individuals in the high WC group showed higher leptin levels (p = 0.003) and higher HOMA-IR (p = 0.024) compared to the low WC group. Conclusion: Increased WC in healthy young individuals was associated with reduced GFR and RPF likely mediated by increased RVR.
CRIS-Team Scopus Importer:2024-03-08
Keywords: Clearance analysis; Obesity; Renal hemodynamic; Waist circumference

Renal and intraglomerular haemodynamics in chronic heart failure with preserved and reduced ejection fraction - Jung, Susanne; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Kannenkeril, Dennis; Schuster, Tizia; Ott, Christian; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims: Congestive heart failure (CHF) and impaired renal function are two often co-existing medical conditions and associated with adverse cardiovascular outcome. The aim of the current study was to assess renal and intraglomerular haemodynamics by constant infusion input clearance technique in subjects with CHF. Methods and results: The group of subjects with CHF consisted of 27 individuals with HFpEF and 27 individuals with HFrEF and were compared with 31 healthy controls. Subjects underwent renal clearance examination to measure glomerular filtration rate (GFR) and renal blood and plasma flow (RBF and RPF) and to calculate intraglomerular haemodynamics such as resistances of the afferent (RA) and efferent arterioles (RE) as well as intraglomerular pressure (Pglom). Measured GFR was lower in CHF subjects (68.1 ± 10.1 mL/min/1.73 m2) compared with controls (83.6 ± 13.4 mL/min/1.73 m2, Padj < 0.001) as was Pglom (Padj < 0.001). Total renal vascular resistance (RVR) was higher in CHF subjects (87.3 ± 20.1 vs. 73.8 ± 17.1 dyn × s/cm5, Padj < 0.001) mediated by an increased resistance at the afferent site (3201 ± 1084 vs. 2181 ± 796 dyn × s/cm5, Padj < 0.001). Comparing HFpEF and HFrEF subjects, RA was higher in HFrEF subjects. The severity of CHF assessed by NT-proBNP revealed an inverse association with renal perfusion (RPF r = −0.421, P = 0.002, RBF r = −0.414, P = 0.002) and a positive relation with RVR (r = 0.346, P = 0.012) at the post-glomerular site (RE: r = 0.318, P = 0.022). Conclusions: Renal function assessed by measured GFR is reduced and renal vascular resistance at the preglomerular, afferent site is increased in HFpEF and, to greater extent, in HFrEF. Our data indicate a close cardiorenal interaction in CHF.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Cardiorenal interaction; Heart failure; Preserved ejection fraction; Reduced ejection fraction; Renal haemodynamics

Renal Denervation for Resistant Hypertension: Past, Present, and Future - Ott, Christian; Schmieder, Roland (Current Hypertension Reports, 2015)
Renal denervation (RDN) for treatment of resistant hypertension was introduced only 5 years ago. A clear pathophysiological role of renal sympathetic activity for the initiation and maintenance of hypertension and promising data showing a substantial and sustained blood pressure (BP) reduction after RDN has promoted the widespread use of the method at least in Europe. However, in a pivotal trial that included a sham-control group, no significant BP lowering effects was observed. Afterwards, it became clear that methodological issues and poor performance and execution of the intervention have hampered the results of Symplicity HTN-3 study, thereby limiting its validity profoundly. Now, in 2015, the renaissance of RDN has begun and new randomized prospective clinical trials have or will be started soon. In the meantime, it may be wise not to ignore all previous findings, as a rescue therapy for treatment resistant hypertension. A new science era emerged, with changes of the interventional approach and selection of patients potentially profiting most from RDN.
EVALuna2:3795

Renal denervation improves 24-hour central and peripheral blood pressures, arterial stiffness, and peripheral resistance - Ott, Christian; Franzen, Klaas F.; Graf, Tobias; Weil, Joachim; Schmieder, Roland; Reppel, Michael; Mortensen, Kai (Journal of Clinical Hypertension, 2018)
Ambulatory blood pressure (BP) and central BP are better predictors for overall cardiovascular risk and mortality than brachial BP. Renal denervation (RDN) has been shown to reduce office brachial and central BP as well as brachial ambulatory BP, but data on central ambulatory BP are limited. Patients (N = 94) with treatment resistant hypertension (TRH) who underwent RDN were included. Ambulatory BP, including central pressures, hemodynamics, and arterial stiffness were measured at baseline and 3, 6, 12 months after RDN by an oscillometric device (MobiloGraph™). At 3, 6, and 12-month follow-ups, brachial ambulatory BP was reduced (P for all < .001). Consistently, central ambulatory BP was reduced (P for all < .001). Ambulatory assessed averaged daytime pulse wave velocity improved after RDN (P < .05). Total vascular resistance decreased (P for all < .01). In patients with TRH, RDN improves brachial and central ambulatory BP, arterial stiffness, and total vascular resistance, indicating an improvement of cardiovascular outcome.
EVALuna2:33738

Renal denervation in hypertensive patients not on blood pressure lowering drugs - De Jager, Rosa L.; Sanders, Margreet F.; Bots, Michiel L.; Lobo, Melvin D.; Ewen, Sebastian; Beeftink, Martine M. A.; Boehm, Michael; Daemen, Joost; Doerr, Oliver; Hering, Dagmara; Mahfoud, Felix; Nef, Holger; et al. (Clinical Research in Cardiology, 2016)
Studies on the blood pressure lowering effect of renal denervation (RDN) in resistant hypertensive patients have produced conflicting results. Change in medication usage during the studies may be responsible for this inconsistency. To eliminate the effect of medication usage on blood pressure we focused on unmedicated hypertensive patients who underwent RDN.Our study reports on a cohort of patients, who were not on blood pressure lowering drugs at baseline and during follow-up, from eight tertiary centers. Data of patients were used when they were treated with RDN and had a baseline office systolic blood pressure (SBP) >=140 mmHg and/or 24-h ambulatory SBP >=130 mmHg. Our primary outcome was defined as change in office and 24-h SBP at 12 months after RDN, compared to baseline. Fifty-three patients were included. There were three different reasons for not using blood pressure lowering drugs: (1) documented intolerance or allergic reaction (57 %); (2) temporary cessation of medication for study purposes (28 %); and (3) reluctance to take antihypertensive drugs (15 %). Mean change in 24-h SBP was -5.7 mmHg [95 % confidence interval (CI) -11.0 to -0.4; p = 0.04]. Mean change in office SBP was -13.1 mmHg (95 % CI -20.4 to -5.7; p = 0.001). No changes were observed in other variables, such as eGFR, body-mass-index and urinary sodium excretion.This explorative study in hypertensive patients, who are not on blood pressure lowering drugs, suggests that at least in some patients RDN lowers blood pressure.
EVALuna2:3850

Renal denervation in moderate treatment-resistant hypertension - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Spies, Aline; Ukena, Christian; Laufs, Ulrich; Uder, Michael; Boehm, Michael; Schmieder, Roland (Journal of the American College of Cardiology, 2013)
Objectives This study sought to investigate the effect of renal denervation (RDN) in patients with treatment-resistant hypertension according to the established definition (Joint National Committee VII and European Society of Hypertension/European Society of Cardiology guidelines), that is, office blood pressure (BP) ≥140/90 mm Hg (with at least three antihypertensive drugs, including a diuretic, in adequate doses) and confirmed by 24-h ambulatory BP monitoring (ABPM). Background RDN emerged as an innovative interventional antihypertensive therapy. However, so far, only patients with severe hypertension (systolic BP ≥160 mm Hg or ≥150 mm Hg for patients with type 2 diabetes) have been investigated. Methods In this study, there were 54 patients with moderate treatment-resistant hypertension (office BP ≥140/90 mm Hg and <160/100 mm Hg and diagnosis confirmed by 24-h ABPM of ≥130/80 mm Hg) who underwent catheter-based RDN using the Symplicity catheter (Medtronic Inc., Mountain View, California). Results Patients were treated with 5.1 ± 1.4 antihypertensive drugs on average. Office BP was significantly reduced by 13/7 mm Hg 6 months after RDN (systolic: 151 ± 6 mm Hg vs. 138 ± 21 mm Hg, p < 0.001; diastolic: 83 ± 11 mm Hg vs. 75 ± 11 mm Hg, p < 0.001). In patients (n = 36) who underwent ABPM 6 months after treatment, there was a reduction in average 24-h ABPM by 14/7 mm Hg (systolic: 150 ± 16 mm Hg vs. 136 ± 16 mm Hg, p < 0.001; diastolic: 83 ± 10 mm Hg vs. 76 ± 10 mm Hg, p < 0.001). In 51% of patients, office BP was controlled below 140/90 mm Hg after RDN. In addition, heart rate decreased from 67 ± 11 to 63 ± 10 beats/min (p = 0.006). Conclusions Our data indicate that RDN may reduce office and 24-h ambulatory BP substantially in patients with moderate treatment-resistant hypertension. (Renal Denervation in Treatment Resistant Hypertension; NCT01687725). © 2013 by the American College of Cardiology Foundation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 24-h ambulatory blood pressure; renal denervation; treatment-resistant hypertension

Renal denervation in patients with versus without chronic kidney disease: results from the Global SYMPLICITY Registry with follow-up data of 3 years - Ott, Christian; Mahfoud, Felix; Mancia, Giuseppe; Narkiewicz, Krzysztof; Ruilope, Luis M.; Fahy, Martin; Schlaich, Markus P.; Böhm, Michael; Schmieder, Roland (Nephrology Dialysis Transplantation, 2022)
BACKGROUND: Activity of the sympathetic nervous system is increased in patients with hypertension and chronic kidney disease (CKD). Here we compare short- and long-term blood pressure (BP)-lowering effects of renal denervation (RDN) between hypertensive patients with or without CKD in the Global SYMPLICITY Registry. METHODS: Office and 24-h ambulatory BP (ABP) were assessed at prespecified time points after RDN. The presence of CKD was defined according to the estimated glomerular filtration rate (eGFR) and enrolled patients were stratified based on the presence (n = 475, eGFR <60 mL/min/1.73 m2) or absence (n = 1505, eGFR ≥60mL/min/1.73 m2) of CKD. RESULTS: Patients with CKD were older (P < 0.001) and were prescribed more antihypertensive medications (P < 0.001). eGFR decline per year was not significantly different between groups after the first year. Office and 24-h ABP were significantly reduced from baseline at all time points after RDN in both groups (all P < 0.001). After adjusting for baseline data, patients without CKD had a greater reduction in office systolic BP (-17.3 ± 28.3 versus -11.7 ± 29.9 mmHg; P = 0.009) but not diastolic BP at 36 months compared with those with CKD. Similar BP and eGFR results were found when the analysis was limited to patients with both baseline and 36-month BP data available. There was no difference in the safety profile of the RDN procedure between groups. CONCLUSIONS: After adjusting for baseline data, 24-h systolic and diastolic ABP reduction were similar in patients with and without CKD after RDN, whereas office systolic but not diastolic BP was reduced less in patients with CKD. We conclude that RDN is an effective antihypertensive treatment option in CKD patients.
CRIS-Team Scopus Importer:2022-02-11
Keywords: blood pressure; hypertension; renal function

Renal denervation preserves renal function in patients with chronic kidney disease and resistant hypertension - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Toennes, Stefan W.; Ewen, Sebastian; Ditting, Tilmann; Veelken, Roland; Ukena, Christian; Uder, Michael; Boehm, Michael; Schmieder, Roland (Journal of Hypertension, 2015)
Arterial hypertension and increased sympathetic activity are underlying pathogenetic mechanisms of the progressive loss of renal function in patients with chronic kidney disease (CKD). Meta-analyses have shown that impaired renal function is an independent cardiovascular risk factor. We hypothesized that renal denervation (RDN) decreases the decline of renal function in patients with CKD stages 3 and 4 and treatment-resistant hypertension.We performed an observational study of 27 patients with CKD stages 3 and 4, office blood pressure (BP) >= 140/90 mmHg, while on at least three antihypertensive drug classes including diuretic, and diagnosis confirmed by 24-h ambulatory BP measurement >= 130/80 mmHg. All patients underwent catheter-based RDN using the Symplicity Flex RDN System (Medtronic Inc., Santa Rosa, California, USA). Renal function was evaluated for up to 3 years prior and 1 year after RDN. The change in estimated glomerular filtration rate (eGFR) was calculated by regression slope individually for each patient before and after RDN. The study was registered at http://www.clinicaltrials.gov (ID: NCT01442883).Mean baseline BP was 156 ± 12/82 ± 13 mmHg, despite treatment with 6.2 ± 1.1 antihypertensive drugs. One year after RDN, office BP was reduced by 20 ± 20 (P < 0.001)/8 ± 14 mmHg (P = 0.005) and average 24-h ambulatory BP by 9 ± 14 (P = 0.009)/4 ± 7 mmHg (P = 0.019). Before RDN, eGFR declined by -4.8 ± 3.8 ml/min per 1.73 m per year, and after RDN eGFR improved by +1.5 ± 10 ml/min per 1.73 m at 12 months (P = 0.009).Our observational pilot study in patients with CKD stages 3 and 4 indicates that treatment of hypertension with RDN decreases BP and slows or even halts the decline of renal function.
EVALuna2:3767

RENAL HEMODYNAMIC CHANGES AFTER RENAL DENERVATION - Schmieder, R. S.; Schmid, Axel; Janka, Rolf Matthias; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland; Ott, Christian (2016)
EVALuna2:34706

Renal hemodynamic effects differ between antidiabetic combination strategies: randomized controlled clinical trial comparing empagliflozin/linagliptin with metformin/insulin glargine - Ott, Christian; Jung, Susanne; Korn, Manuel; Kannenkeril, Dennis; Bosch, Agnes; Kolwelter, Julie; Striepe, Kristina; Bramlage, Peter; Schiffer, Mario; Schmieder, Roland (Cardiovascular Diabetology, 2021)
Background: Type 2 diabetes causes cardio-renal complications and is treated with different combination therapies. The renal hemodynamics profile of such combination therapies has not been evaluated in detail. Methods: Patients (N = 97) with type 2 diabetes were randomized to receive either empagliflozin and linagliptin (E+L group) or metformin and insulin glargine (M+I group) for 3 months. Renal hemodynamics were assessed with para-aminohippuric acid and inulin for renal plasma flow (RPF) and glomerular filtration rate (GFR). Intraglomerular hemodynamics were calculated according the Gomez´ model. Results: Treatment with E+L reduced GFR (p = 0.003), but RPF remained unchanged (p = 0.536). In contrast, M+I not only reduced GFR (p = 0.001), but also resulted in a significant reduction of RPF (p < 0.001). Renal vascular resistance (RVR) decreased with E+L treatment (p = 0.001) but increased with M+I treatment (p = 0.001). The changes in RPF and RVR were different between the two groups (both padjust < 0.001). Analysis of intraglomerular hemodynamics revealed that E+L did not change resistance of afferent arteriole (RA) (p = 0.116), but diminished resistance of efferent arterioles (RE) (p = 0.001). In M+I group RA was increased (p = 0.006) and RE remained unchanged (p = 0.538). The effects on RA (padjust < 0.05) and on RE (padjust < 0.05) differed between the groups. Conclusions: In patients with type 2 diabetes and preserved renal function treatment with M+I resulted in reduction of renal perfusion and increase in vascular resistance, in contrast to treatment with E+I that preserved renal perfusion and reduced vascular resistance. Moreover, different underlying effects on the resistance vessels have been estimated according to the Gomez model, with M+I increasing RA and E+L predominantly decreasing RE, which is in contrast to the proposed sodium-glucose cotransporter 2 inhibitor effects. Trial registration: The study was registered at www.clinicaltrials.gov (NCT02752113) on April 26, 2016
CRIS-Team Scopus Importer:2021-09-17
Keywords: Hemodynamics; Intraglomerular; Renal; Type 2 diabetes

Response to letter regarding article, "ambulatory blood pressure changes after renal sympathetic denervation in patients with resistant hypertension" - Mahfoud, Felix; Ukena, Christian; Schmieder, Roland; Cremers, Bodo; Rump, Lars C.; Vonend, Oliver; Weil, Joachim; Schmidt, Martin; Hoppe, Uta C.; Zeller, Thomas; Bauer, Axel; Ott, Christian; et al. (Circulation, 2014)
EVALuna2:3677

Responsiveness of afferent renal nerve units in renovascular hypertension in rats - Rodionova, Kristina; Hilgers, Karl Friedrich; Rafii-Tabrizi, Salman; Doellner, Johannes; Cordasic, Nada; Linz, Peter; Karl, Annalena; Ott, Christian; Schmieder, Roland; Schiffer, Mario; Amann, Kerstin Ute; Veelken, Roland; et al. (Pflügers Archiv: European Journal of Physiology, 2021)
Previous data suggest that renal afferent nerve activity is increased in hypertension exerting sympathoexcitatory effects. Hence, we wanted to test the hypothesis that in renovascular hypertension, the activity of dorsal root ganglion (DRG) neurons with afferent projections from the kidneys is augmented depending on the degree of intrarenal inflammation. For comparison, a nonhypertensive model of mesangioproliferative nephritis was investigated. Renovascular hypertension (2-kidney, 1-clip [2K1C]) was induced by unilateral clipping of the left renal artery and mesangioproliferative glomerulonephritis (anti-Thy1.1) by IV injection of a 1.75-mg/kg BW OX-7 antibody. Neuronal labeling (dicarbocyanine dye [DiI]) in all rats allowed identification of renal afferent dorsal root ganglion (DRG) neurons. A current clamp was used to characterize neurons as tonic (sustained action potential [AP] firing) or phasic (1-4 AP) upon stimulation by current injection. All kidneys were investigated using standard morphological techniques. DRG neurons exhibited less often tonic response if in vivo axonal input from clipped kidneys was received (30.4% vs. 61.2% control, p < 0.05). However, if the nerves to the left clipped kidneys were cut 7 days prior to investigation, the number of tonic renal neurons completely recovered to well above control levels. Interestingly, electrophysiological properties of neurons that had in vivo axons from the right non-clipped kidneys were not distinguishable from controls. Renal DRG neurons from nephritic rats also showed less often tonic activity upon current injection (43.4% vs. 64.8% control, p < 0.05). Putative sympathoexcitatory and impaired sympathoinhibitory renal afferent nerve fibers probably contribute to increased sympathetic activity in 2K1C hypertension.
CRIS-Team WoS Importer:2021-07-23

Retinal Capillary Rarefaction in Patients with Type 2 Diabetes Mellitus - Jumar, Agnes; Harazny, Joanna M.; Ott, Christian; Friedrich, Stefanie; Kistner, Iris; Striepe, Kristina; Schmieder, Roland (PLoS ONE, 2016)
In diabetes mellitus type 2, capillary rarefaction plays a pivotal role in the pathogenesis of end-organ damage. We investigated retinal capillary density in patients with early disease.This cross-sectional study compares retinal capillary rarefaction determined by intercapillary distance (ICD) and capillary area (CapA), measured non-invasively and in vivo by scanning laser Doppler flowmetry, in 73 patients with type 2 diabetes, 55 healthy controls and 134 individuals with hypertension stage 1 or 2.In diabetic patients, ICD was greater (23.2±5.5 vs 20.2±4.2, p = 0.013) and CapA smaller (1592±595 vs 1821±652, p = 0.019) than in healthy controls after adjustment for differences in cardiovascular risk factors between the groups. Compared to hypertensive patients, diabetic individuals showed no difference in ICD (23.1±5.8, p = 0.781) and CapA (1556±649, p = 0.768).In the early stage of diabetes type 2, patients showed capillary rarefaction compared to healthy individuals.
EVALuna2:3920

Retinal microperfusion after renal denervation in treatment-resistant hypertensive patients - Ott, Christian; Harazny, Joanna M.; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Bladowski, Marek; Michelson, Georg; Uder, Michael; Schmieder, Roland (Clinical Research in Cardiology, 2015)
High pulsatile pressure and flow in the arteries causes microvascular damage, and hence increased cardio-, and cerebrovascular complications. With advanced stages of hypertensive disease, an exaggerated pulsatile retinal capillary flow (RCF) has been shown, but data about interventional effect are missing.Fifty-one patients with true treatment-resistant hypertension (TRH) underwent renal denervation (RDN) using the Symplicity Flex(TM) catheter and were followed for 12 months. RCF was assessed non-invasively using Scanning laser Doppler flowmetry (SLDF) before, 6 (6 M), and 12 (12 M) months after RDN. RCF was measured in systole and diastole and pulsed RCF (difference of RCF in systole minus diastole) was calculated. In addition, flicker light-induced vasodilation (representing vasodilatory capacity) was assessed.Systolic and diastolic office blood pressure (BP) as well as 24-h ABPM decreased significantly 6 M and 12 M after RDN, compared to baseline values (all p < 0.001). There was a significant reduction of pulsed RCF 6 M (231 ± 81 versus 208 ± 68 AU, p = 0.046) and 12 M (194 ± 72 AU, p = 0.001) after RDN, whereas the mean RCF was unchanged. Moreover, there was a significant increase of flicker light-induced vasodilation after RDN (p = 0.043).In hypertensive patients with TRH, we observed a decrease of pulsed RCF 6 M and 12 M after RDN and an increase of vasodilatory capacity, in parallel to decreases in BP and heart rate. The reduction of pulsed RCF after RDN implies a decrease of shear stress on the vascular wall by the pulsed blood flow. This and the increment of vasodilatory capacity suggest an improvement of retinal (and potentially cerebral) microcirculation.
EVALuna2:3762

Retinal neurodegeneration in patients with end-stage renal disease assessed by spectral-domain optical coherence tomography - Jung, Susanne; Bosch, Agnes; Ott, Christian; Kannenkeril, Dennis; Dienemann, Thomas; Harazny, Joanna M.; Michelson, Georg; Schmieder, Roland (Scientific Reports, 2020)
Spectral-domain optical coherence tomography (SD-OCT) represents a reliable tool for retinal layer volume and thickness measurement. The aim of this study was to evaluate retinal changes indicating neurodegenerative processes in patients with end-stage renal disease (ESRD) compared to healthy controls. This was a cross-sectional, single-center study comprising 32 ESRD patients and 38 controls. Sectoral retinal nerve fiber layer (RNFL) thickness and retinal layer volumes were obtained by SD-OCT. Age- and gender-adjusted retinal layer volumes such as total retinal volume (p = 0.037), ganglion cell layer volume (GCL, p = 0.003), ganglion cell layer – inner plexiform layer volume (GCL-IPL, p = 0.005) and inner retinal layer volume (IRL, p = 0.042) of the right eye were lower in ESRD patients. Inner plexiform layer volume of both eyes (IPL, right eye: p = 0.017; left eye: 0.044) was reduced, as was RNFL thickness in the temporal superior sector (right eye: p = 0.016). A subgroup analysis excluding patients with diabetes revealed that GCL (p = 0.014) and GCL-IPL volume of the right eye (p = 0.024) and temporal superior sector of the RNFL scan (p = 0.021) in ESRD patients were still significantly thinner. We observed a decrease in several retinal layer volumes and temporal RNFL thickness indicative of retinal neurodegenerative processes in patients with ESRD.
CRIS-Team Scopus Importer:2020-04-03

Retinal vascular resistance in arterial hypertension - Kannenkeril, Dennis; Harazny, Joanna M.; Bosch, Agnes; Ott, Christian; Michelson, Georg; Schmieder, Roland; Friedrich, Stefanie (Blood Pressure, 2017)
Retinal microcirculation represents an easily accessible, non-invasive, in-vivo possibility to assess early microvascular changes. In addition to the assessment of functional (e.g. retinal capillary flow, RCF) and retinal arteriolar structural parameters (e.g. wall-to-lumen-ratio, WLR) we now suggest a new parameter reflecting the resistance in small retinal arterioles (RVR).In 45 normotensive (NT) subjects and 123 patients with hypertension stage 1 (HT) we assessed RCF, WLR, arteriolar diameter, lumen diameter and wall cross section area in the retinal circulation by using scanning laser Doppler flowmetry (SLDF). Mean arterial pressure (MAP) was measured immediately before the SLDF measurement and retinal vascular resistance was calculated (RVR = MAP/RCF). In a separate study the test-retest reliability was determined in 6 volunteers from our clinical staff by assessing RVR three times within six weeks.The analysis of the volunteers revealed a coefficient of variation for RVR of 7.75 ± 2.11% and Cronbach´s alpha was 0.90. WLR, a marker of vascular remodeling did not differ between NT and HT. In contrast, RCF and inner diameter of the retinal arterioles (ID) were significantly lower (RCF: p = .045 and ID: p = .001) in the HT group than in the NT group and RVR was significantly higher in the HT group than in the NT group (p < .001). In both groups we found no correlation of RVR with age, but a significant correlation of RVR with WLR (NT: r = 0.34, p = .006; HT: r = 0.25, p = .01), indicating that the RVR reflects vascular remodeling in the retinal circulation.Our data showed an increased retinal vascular resistance in hypertensive patients compared to non-hypertensive patients prior to the occurrence of structural retinal vascular remodeling. The correlation between RVR and WLR indicates that RVR is a reliable, non-invasive and early-sensitive marker of vascular remodeling in early hypertension.
EVALuna2:4030

Sex Differences in Blood Pressure and Potential Implications for Cardiovascular Risk Management - Picone, Dean S.; Stoneman, Elif; Cremer, Antoine; Schultz, Martin G.; Otahal, Petr; Hughes, Alun D.; Black, J. Andrew; Bos, Willem Jan; Chen, Chen Huan; Cheng, Hao Min; Dwyer, Nathan; Lacy, Peter; et al. (Hypertension, 2023)
BACKGROUND: Accurate blood pressure (BP) measurement is critical for optimal cardiovascular risk management. Age-related trajectories for cuff-measured BP accelerate faster in women compared with men, but whether cuff BP represents the intraarterial (invasive) aortic BP is unknown. This study aimed to determine the sex differences between cuff BP, invasive aortic BP, and the difference between the 2 measurements. METHODS: Upper-arm cuff BP and invasive aortic BP were measured during coronary angiography in 1615 subjects from the Invasive Blood Pressure Consortium Database. This analysis comprised 22 different cuff BP devices from 28 studies. RESULTS: Subjects were 64±11 years (range 40-89) and 32% women. For the same cuff systolic BP (SBP), invasive aortic SBP was 4.4 mm Hg higher in women compared with men. Cuff and invasive aortic SBP were higher in women compared with men, but the sex difference was more pronounced from invasive aortic SBP, was the lowest in younger ages, and the highest in older ages. Cuff diastolic blood pressure overestimated invasive diastolic blood pressure in both sexes. For cuff and invasive diastolic blood pressure separately, there were sex*age interactions in which diastolic blood pressure was higher in younger men and lower in older men, compared with women. Cuff pulse pressure underestimated invasive aortic pulse pressure in excess of 10 mm Hg for both sexes in older age. CONCLUSIONS: For the same cuff SBP, invasive aortic SBP was higher in women compared with men. How this translates to cardiovascular risk prediction needs to be determined, but women may be at higher BP-related risk than estimated by cuff measurements.
CRIS-Team Scopus Importer:2023-01-27
Keywords: diagnostic equipment; hypertension; physiology; pulse wave analysis; sex factors

SGLT-2-inhibition with dapagliflozin reduces tissue sodium content: a randomised controlled trial - Karg, Margarete; Bosch, A.; Kannenkeril, Dennis; Striepe, Kristina; Ott, Christian; Schneider, M. P.; Boemke-Zelch, Franziska; Linz, Peter; Nagel, Armin Michael; Titze, Jens; Uder, Michael; Schmieder, Roland (Cardiovascular Diabetology, 2018)
Sodium tissue content by 23Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes characterized by sodium retention leads to decreased tissue sodium content due to its pharmacological action.In a prospective double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to either dapagliflozin 10 mg or placebo once daily for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analysed the sodium content in the skin and muscles of the lower leg by Na-MRI.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11 mmHg, p = 0.010), and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024), 24-h ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline [24.1 ± 6.6 vs. 22.7 ± 6.4 A.U.(arbitrary unit) p = 0.013]. No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 A.U. p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in tissue sodium content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT02383238) retrospectively registered.
EVALuna2:4043

Skin sodium content as a predictor of blood pressure response to renal denervation - Günes-Altan, Merve; Schmid, Axel; Kannenkeril, Dennis; Linz, Peter; Ott, Christian; Bosch, Agnes; Schiffer, Mario; Uder, Michael; Schmieder, Roland (Hypertension Research, 2023)
Patients with treatment resistant hypertension (TRH) are known to have elevated sodium (Na) content in muscle and skin. Renal denervation (RDN) emerged as an adjacent therapeutic option in this group of patients. This analysis aimed at evaluating whether tissue Na content predicts blood pressure (BP) response after RDN in patients with TRH. Radiofrequency-device based RDN was performed in 58 patients with uncontrolled TRH. Office and 24-h ambulatory BP were measured at baseline and after 6 months. To assess tissue Na content Na magnetic resonance imaging (Na-MRI) was performed at baseline prior to RDN. We splitted the study cohort into responders and non-responders based on the median of systolic 24-h ambulatory blood pressure (ABP) reduction after 6 months and evaluated the association between BP response to RDN and tissue Na content in skin and muscle. The study was registered at http://www.clinicaltrials.gov (NCT01687725). Six months after RDN 24-h ABP decreased by −8.6/−4.7 mmHg. BP-Responders were characterized by the following parameters: low tissue sodium content in the skin (p = 0.040), female gender (p = 0.027), intake of aldosterone antagonists (p = 0.032), high baseline 24-h night-time heart rate (p = 0.045) and high LDL cholesterol (p < 0.001). These results remained significant after adjustment for baseline 24-h systolic BP. Similar results were obtained when the median of day-time and night-time ABP reduction after 6 months were used as cut-off criteria for defining BP response to RDN. We conclude that in addition to clinical factors including baseline 24-h ABP Na-MRI may assist to select patients with uncontrolled TRH for RDN treatment. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-11-03
Keywords: Renal denervation; Sodium MRI; Tissue sodium

The authors reply - Ott, Christian; Schmieder, Roland (Kidney International, 2022)
CRIS-Team Scopus Importer:2022-04-01

The effect of renal denervation in moderate treatment-resistant hypertension with confirmed medication adherence - Ott, Christian; Mahfoud, Felix; Schmid, Andrea; Ewen, Sebastian; Toennes, Stefan W.; Meyer, Markus R.; Helfer, Andreas G.; Maurer, Hans H.; Ditting, Tilmann; Veelken, Roland; Zivanovic, Ina; Uder, Michael; et al. (Journal of Hypertension, 2016)
Data on the blood pressure (BP)-lowering effect of renal denervation (RDN) in moderate treatment-resistant hypertension (TRH) are limited. Moreover, change of adherence to medication, as one potential confounder of BP response, has never been analyzed rigorously in this group of patients. We analyzed the effect of RDN on BP in patients with moderate TRH who were retrospectively found to be completely adherent to their antihypertensive medication.Our study cohort comprised 40 patients with moderate TRH [office BP >= 140/90 but <160/100 mmHg and 24-h ambulatory BP monitoring (ABPM) >=130/80 mmHg] who underwent catheter-based RDN. Further major inclusion criterion was complete adherence to their medication (>=80% intake of their prescribed antihypertensive drugs) at baseline (assessed by retrospective toxicological analysis).Six months after RDN, office BP was reduced by -10/-6 mmHg (SBP: 149 ± 6 vs. 139 ± 15 mmHg; DBP: 81 ± 12 vs. 75 ± 10 mmHg; both P < 0.001) and 24-h ABPM by -7/-4 mmHg (SBP: 150 ± 14 vs. 143 ± 16 mmHg, P = 0.005; DBP: 82 ± 10 vs. 78 ± 9 mmHg, P = 0.009). Number of prescribed antihypertensive medication [6.0 (5.0-6.0) vs. 5.5 (5.0-6.0), P = 0.013] and adherence rate (95.2 ± 7.6 vs. 91.7 ± 13.9%, P = 0.065) was slightly reduced 6 months after RDN, both likely to underestimate the true BP reduction.Thus, our data indicate that even after given full respect to drug adherence as potential confounder of BP response after RDN, both office and 24-h ABPM were substantially reduced in patients with moderate TRH.
EVALuna2:3907

The effect of sacubitril/valsartan compared to olmesartan on cardiovascular remodelling in subjects with essential hypertension: the results of a randomized, double-blind, active-controlled study - Schmieder, Roland; Wagner, Frank; Mayr, Michael; Delles, Christian; Ott, Christian; Keicher, Christian; Hrabak-Paar, Maja; Heye, Tobias; Aichner, Solveig; Khder, Yasser; Yates, Denise; Albrecht, Diego; et al. (European Heart Journal, 2017)
Progressive aortic stiffening eventually leads to left ventricular (LV) hypertrophy and heart failure if left untreated. Anti-hypertensive agents have been shown to reverse this to some extent. The effects of sacubitril/valsartan (LCZ696), a dual-action angiotensin receptor blocker (ARB), and neprilysin inhibitor, on arterial stiffness and LV remodelling have not been investigated.This was a randomized, multi-centre, double-blind, double-dummy, active-controlled, parallel group, study to compare the effects on cardiovascular remodelling of sacubitril/valsartan with those of olmesartan in patients with hypertension and elevated pulse pressure. Magnetic resonance imaging scans were used to assess LV mass and local aortic distensibility, at baseline and at 12 and 52 weeks after initiation of treatment. Central pulse and systolic pressure were determined using a SphymoCor® XCEL device at each time point. A total of 114 patients were included, with 57 in each treatment group. The mean age was 59.8 years, and 67.5% were male. Demographic characteristics did not vary between the two sets of patients. Left ventricular mass index decreased to a greater extent in the sacubitril/valsartan group compared to the olmesartan group from baseline to 12 weeks (-6.36 vs. -2.32 g/m2; P = 0.039) and from baseline to 52 weeks (-6.83 vs. -3.55 g/m2; P = 0.029). These differences remained significant after adjustment for systolic blood pressure (SBP) at follow-up (P = 0.036 and 0.019 at 12 and 52 weeks, respectively) and similar signals (though formally non-significant) were observed after adjusting for changes in SBP (P = 0.0612 and P = 0.0529, respectively). There were no significant differences in local distensibility changes from baseline to 12 or 52 weeks between the two groups; however, there was a larger reduction in central pulse pressure for the sacubitril/valsartan group compared to the olmesartan group (P = 0.010).Since LV mass change correlates with cardiovascular prognosis, the greater reductions in LV mass indicate valuable advantages of sacubitril/valsartan compared to olmesartan. The finding that LV mass index decrease might be to some extent independent of SBP suggests that the effect of the dual-acting agent may go beyond those due to its BP-lowering ability.
EVALuna2:3950

The influence of aircraft noise exposure on the systemic and renal haemodynamics - Bosch, Agnes; Kannenkeril, Dennis; Jung, Susanne; Striepe, Kristina; Karg, Marina V.; Ott, Christian; Schmieder, Roland (European Journal of Preventive Cardiology, 2022)
Aims: Epidemiological studies found a link between aircraft noise exposure and increased incidence of arterial hypertension and cardiovascular disease, but the underlying pathophysiological mechanisms are not fully understood. Clinical studies have shown that mental stress affects the systemic and renal haemodynamic, but no such study was performed with noise exposure as stress factor. We analysed systemic and renal effects of 25 min standardized aircraft noise in a sham controlled clinical study including 80 healthy men and 34 male patients with hypertension. Methods and results: Systemic haemodynamic parameters were measured using electrocardiography and impedance cardiography. The renal haemodynamic was assessed using steady state input clearance with infusion of para-aminohippuric acid and inulin for glomerular filtration rate and renal plasma flow, respectively. In the systemic circulation of hypertensive patients, there was an increase in total peripheral resistance (TPR) (1420 ± 387 vs. 1640 ± 516 dyn·s·cm-5, P = 0.001) and a decrease in cardiac index (CI) (2.9 ± 0.8 vs. 2.6 ± 0.8 L/(min·m2, P < 0.001) 25 min after the start of noise exposure, which was not present during sham procedure (P = 0.10, P = 0.86). In healthy individuals a procedure induced increase in TPR and decrease in CI was present after noise (TPR: 995 ± 239 vs. 1106 ± 308 dyn·s·cm-5, P = 0.001, CI: 3.6 ± 0.7 vs. 3.3 ± 0.9 L/(min·m2, P < 0.001) and sham application (TPR: P = 0.002, CI: P < 0.001). However, in healthy individuals changes in TPR (P = 0.450) and CI (P = 0.605) from baseline until 25 min after the start of the intervention did not differ between noise and sham exposure. In the renal circulation of hypertensive patients and healthy individuals the response did not differ between noise and sham procedure. Conclusions: In hypertensive but not healthy men we observed a systemic vasoconstrictive response after aircraft noise exposure accompanied by a decrease in CI. No significant changes were observed in the renal circulation. Our results suggest that male hypertensive patients are more susceptible for noise-induced changes of vascular resistance in the systemic circulation.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Aircraft noise; Clearance; Hypertension; Renal haemodynamic; Systemic haemodynamic

THE INFLUENCE OF ANNOYANCE DUE TO AIRCRAFT NOISE ON RENAL HEMODYNAMIC - Bosch, Agnes; Kannenkeril, Dennis; Ott, Christian; Harazny, J. M.; Striepe, Kristina; Karg, M. V.; Jung, Susan; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20

THE SGLT2 INHIBITOR EMPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

The SGLT2 inhibitor empagliflozin reduces tissue sodium content in patients with chronic heart failure: results from a placebo-controlled randomised trial - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Nöh, Lisa; Schiffer, Mario; Uder, Michael; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2022)
Introduction: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have cardiovascular protective properties in addition to the metabolic effects and represent a cornerstone of treating patients with chronic heart failure (CHF). We hypothesised that empagliflozin reduces tissue sodium content in patients with CHF. Methods: In a double-blind, randomised (2:1), placebo-controlled, parallel-group, clinical trial, 74 patients with NYHA class II–III CHF and an ejection fraction of 49% or less received empagliflozin 10 mg once daily or placebo for 3 months. In each patient, tissue sodium content of the lower leg was assessed non-invasively by sodium-MRI (23Na-MRI) at baseline, after 1 and 3 months of treatment. Results: After 1 and 3 months treatment with empagliflozin (n = 48), a significant decrease in skin sodium content was observed (1 month: 22.8 ± 6.1 vs. 21.6 ± 6.0 AU, p = 0.039; 3 months: 22.9 ± 6.1 vs. 21.6 ± 6.1 AU, p = 0.013), while there was no change in muscle sodium and muscle water content. In direct comparison, the change in skin sodium content between baseline and 3 months was − 1.3 ± 3.5 AU in the empagliflozin group versus 0.6 ± 3.5 AU in the placebo group (p for between-group difference = 0.022). No significant difference regarding change in muscle sodium and in muscle water content was observed after 3 months treatment between the two groups. Conclusion: This trial showed a significant decrease in skin sodium content after 1 and 3 months of treatment with empagliflozin. The decrease in skin sodium content may reflect a decrease in subclinical micro-oedema or/and in non-osmotic bound tissue sodium, both reported to impair left ventricular function. Trial registration number: NCT03128528 (http://www.clinicaltrials.gov). Trial registration date: 25th April 2017.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Chronic heart failure; Empagliflozin; Magnetic resonance imaging; SGLT2 inhibitor; Sodium; Tissue sodium content

Tissue sodium concentration correlates with hypertrophic vascular remodelling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susan; Harazny, Jeremy; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

Tissue sodium concentration emerged as a determinant of hypertrophic vascular remodeling in type 2 diabetes - Schmieder, Roland; Jung, Susanne; Kannenkeril, Dennis; Harazny, J. M.; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Angela; Uder, Michael (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Tissue sodium content correlates with hypertrophic vascular remodeling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susanne; Harazny, Joanna; Striepe, Kristina; Ott, Christian; Dahlmann, Anke; Kopp, Christoph; Schiffer, Mario; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2021)
Background: Prospective studies describe a linkage between increased sodium intake and higher incidence of cardiovascular organ damage and end points. We analyzed whether tissue sodium content in the skin and muscles correlate with vascular hypertrophic remodeling, a risk factor for cardiovascular disease.
CRIS-Team WoS Importer:2021-12-03

Tissue sodium content in patients with type 2 diabetes mellitus - Kannenkeril, Dennis; Karg, Marina V.; Bosch, Agnes; Ott, Christian; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2019)
Background: Tissue sodium content by 23 Na magnetic resonance imaging (MRI)has been found to be increased in arterial hypertension. We analyzed whether tissue sodium content is increased in patients with type-2 diabetes (T2DM). Methods: Patients with T2DM were compared to those with primary hypertension. Patients with T2DM were off any antidiabetic and hypertensive patients off any antihypertensive therapy for at least 4 weeks. Skin and muscle sodium content was assessed non-invasively with a 3.0 T clinical MRI system (Magnetom Verio, Siemens Health Care, Erlangen, Germany)in each patient. Results: In patients with T2DM (N = 59)we observed significantly greater muscle sodium content (diabetes: 20.6 ± 3.5 vs hypertension: 16.3 ± 2.5 mmol/l, p < 0.001)and skin sodium content (diabetes: 24.5 ± 7.2 vs hypertension: 20.6 ± 5.7 mmol/l, p = 0.01)than in those with primary hypertension (N = 33). When potential confounders (age, body mass index, gender, systolic and diastolic blood pressure, estimated glomerular filtration rate)were entered in a covariance analysis, both skin sodium content (p = 0.037)and muscle sodium content (p < 0.001)were still clearly elevated. Conclusion: Patients with T2DM have greater skin and muscle sodium content. These are the first known data to demonstrate increased tissue sodium content in patients with T2DM, measured by 23 Na magnetic resonance imaging. Since tissue sodium content is related to organ damage, therapeutic intervention should aim at reducing tissue sodium content.
CRIS-Team Scopus Importer:2019-05-21
Keywords: 23Na-MRI; T2DM; Tissue sodium content; Salt; Sodium retention

Vascular and renal hemodynamic changes after renal denervation - Ott, Christian; Janka, Rolf Matthias; Schmid, Axel; Titze, Stephanie; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Uder, Michael; Schmieder, Roland (Clinical Journal of the American Society of Nephrology, 2013)
Background and objectives Renal denervation (RDN) has been shown to be effective in reducing BP in treatmentresistant hypertension. Measurement of the renal and sympathetic activity revealed a decrease in sympathetic drive to the kidney and small resistance vessels after RDN. However, the consequences on renal perfusion and renal vascular resistance (RVR), as well as central hemodynamics, are unknown. Design, setting, participants, & measurements Nineteen patients with treatment-resistant hypertension (office BP140/90mmHg, despite at least three antihypertensive drugs [including a diuretic], and diagnosis confirmed by 24-hour ambulatory BPmonitoring) underwent RDNbetween January andOctober 2011. Renal perfusion and RVR were noninvasively assessed by magnetic resonance imaging with arterial spin labeling, and renal function was assessed by estimating GFR before (day 21), after (day +1), and again after 3 months of RDN. Central hemodynamics was assessed using pulse wave analysis at day 21 and after 6 months of RDN. Results Peripheral office BP (systolic, 158±26 versus 142±23mmHg, P=0.002; diastolic, 83±13 versus 76±9mmHg, P=0.02) and mean systolic 24-hour ambulatory BP (159±17 versus 152±17 mmHg, P=0.02) were significantly reduced 6 months after RDN. Renal perfusion was not statistically different between day 21 and day +1 (256.8 [interquartile range (IQR), 241-278] versus 263.4 [IQR, 252-277] ml/min per 100 g; P=0.17) as well as after 3 months (256.8 [IQR, 241-278] versus 261.2 [IQR, 240-285] ml/min per 100 g; P=0.27) after RDN. RVR dropped (432.1 [IQR, 359-525] versus 390.6 [IQR, 338-461] AU; P=0.02), whereas renal function was not statistically different at any time point. Central systolic BP (145±31 versus 131628 mmHg; P=0.009), diastolic BP (85±18 versus 80±14 mmHg; P=0.03), and central pulse pressure (61±18 versus 52±18 mmHg; P=0.02) were significantly reduced 6 months after RDN. Central augmentation index (24±8 versus 20±8%; P=0.02) was decreased 6 months after RDN. Conclusion The data indicate that RDN significantly reduced peripheral and central BP. Despite reduced systemic BP, renal perfusion and function did not change after RDN. © 2013 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2023-03-08

VASCULAR REMODELING OF RETINAL VESSELS IN PATIENTS WITH CONGESTIVE HEART FAILURE - Jung, Susan; Kannenkeril, Dennis; Ott, Christian; Cifkova, R.; Harazny, J. M.; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2019)
CRIS-Team WoS Importer:2019-09-20